Comparative techno-economic and life cycle assessment of ammonia co-firing with different ammonia production routes in a 1100 MWe ultra-supercritical CFB coal power plant - Jae-Beom Lee; Jae-Hoon Jeon; Gwon-Woo Lee; Jin-Young Kim; Hye-Rin Kim; Eun-Uk Yu; Sung-Jin Pak; Sang-Jun Han; Shaukat Ali Mazari; Tae-Young Mun; Jong-Ho Moon (Fuel, 2027)

Enzymatic biotransformation of Momordica charantia fruit with enhancement of chemical constituents and anti-adipogenic effects - Gyeong Han Jeong; Hanui Lee; Hyoung-Woo Bai; Seung Sik Lee; Byung Yeoup Chung; Tae Hoon Kim (Phytochemistry Letters, 2026)

Aligning green spaces with human activity: uncovering opportunity-realization mismatches in urban green exposure - Yicheng Zheng; Tao Lin; Nicholas A.S. Hamm; Yuan Chen; Tongyu Zhou; Xiangzhong Guo; Hongkai Geng; Matthew Ng; Hoon Han; Christopher Pettit; Yong-Guan Zhu (Landscape and Urban Planning, 2026)

Highly selective solar CO2 conversion into ethanol over metal-free sulfonated g-C3N4/nitrogen doped reduced graphene oxide hybrid photocatalyst - Sachin G. Ghugal; Amol U. Pawar; Park Kyoung Mo; Poonchi Sivasankaran Ramesh; Harish Reddy Inta; Sanjeev Gupta; Sung-hoon Oh; Muhammad Zaeem Azam Khan; Young Seok Son; Hyunchul Shin; Hongxian Han; Young Soo Kang (Chemical Engineering Journal, 2026)

A pseudo-bilayer organic photoanode for solar water oxidation - Gyu Won Chae; Seong Rae Kang; Jin Su Park; Euimin Lee; Jisu Yoo; Hyuna Kim; Jongbeom Kim; Hoon Kim; Donghyun Lee; Eunsong Jeon; Wonjun Kim; Changduk Yang; et al. (Chemical Engineering Journal, 2026)

Cost-effective upcycling of spent graphite into surface-engineered micro-Si/C composite anodes - Seungmin Lee; Hangeol Jang; Yu-Jin Han; San-Seong Cho; Sungwoo Park; Sang-Hoon Park (Chemical Engineering Journal, 2026)

Beyond Acute Kidney Injury : Direct Pathways Implicate Inflammatory Mechanisms in Serum NGAL’s Mortality Effect in Acute Brain Injury - Hyung Seok Guk; Yong Soo Kim; Dong-Wan Kang; Sang-Hoon Han; Museong Kim; Moon-Ku Han; Kyoungho Suk; Jae-Hong Kim; Han-Gil Jeong (Translational Stroke Research, 2026)

Spatiotemporal migration of slip localization zones along the Hambaeksan Fault, South Korea - Jae Hoon Kim; Jin-Han Ree; Raehee Han; Chowon Park; Dohee Gu; Jusun Woo (Journal of Structural Geology, 2026)

Physicochemical insights into ammonia-amine blending for CO2 capture: Speciation, ammonia volatilization, salt precipitation, and regeneration energy in aqueous NH3-MEA and NH3-AMP solutions - Sang-Jun Han; Hye-Rin Kim; Jin-Young Kim; Jae-Beom Lee; Gwon-Woo Lee; Jae-Hoon Jeon; Shaukat Ali Mazari; Ung Lee; Jong-Ho Moon (Chemical Engineering Journal, 2026)

Age Structure and Growth of the Japanese Spanish Mackerel (Scomberomorus niphonius) in Korean Waters - Han Ju Kim; Hae-young Choi; Seong Yong Moon; Hae Won Lee; Jeong-hoon Lee; Sang Chul Yoon (Fishes, 2026)
In this study, we estimated the age and growth of S. niphonius using otolith-based age determination. Five hundred and thirty individuals were sampled from commercial fisheries and the National Institute of Fisheries Science research vessels in Korean waters between January and December 2024 and from June to September 2025. Fork length ranged from 30.4 to 112.1 cm and body weight ranged from 218.2 to 9360 g. Sagittal otoliths were transversely sectioned and examined under a microscope. The age-reading precision between the two independent readers exhibited a high agreement (percentage agreement = 96.0%, average percentage error = 5.49%, coefficient of variation = 7.76%). The observed age ranges were 0–10.1 years for females and 0–8.1 years for males. Estimated parameters of the von Bertalanffy growth function were L∞=119.77 cm, K=0.41 year−1, and t0=−0.83 for females, and L∞=97.00 cm, K=0.59 year−1, and t0=−0.64 for males. Females exhibited larger asymptotic lengths but lower growth coefficients than those of males, and growth differed significantly between sexes. These results constitute the first study of age and growth based on otoliths in Korean waters and contribute to improving the biological understanding and management of this species.

Mechanistic modeling and characterization of amorphous solid dispersions for nimodipine: preparation methods, physicochemical properties, and in vitro–in vivo exposures - Hari Prasad Bhatta; Ki Hyun Kim; Mansingh Chaudhary; Ki-Taek Kim; Minji Kim; Hea-Young Cho; Ravi Maharjan; Hyo-Kyung Han; Seong Hoon Jeong (Journal of Pharmaceutical Investigation, 2026)

Simultaneous sulfide removal and COD retention of organic sulfur via a pH-controlled MWNTs-assisted sulfidogenic process - Om Prakash; Guryun Jung; Younghun Lee; Seungyeob Han; Dong-Hoon Kim; Seoktae Kang (Journal of Water Process Engineering, 2026)

ATF6 expression governs megakaryocyte maturation through dual regulatory mechanisms - Se-Ryeon Lee; Yu-Seon Lee; Jungsun Kim; Sang Hoon Jeong; Ju-Han Lee; Hwa-Jung Sung; Hong Lee (Molecular & Cellular Toxicology, 2026)

Chloroplast genome characterization of Adenophora taquetii and comparative analysis with related Adenophora species - Song-I Han; Sheikh Mansoor; Jiwon Kim; Nur Azizah Arryanie Binti Morshidi; Jae-Hoon Kim; Kyung-Hwan Boo (Genes & Genomics, 2026)

2025 stratigraphic manual of the Korean South Sea - Jae-Hyuk Lee; Jae-Ho Lee; Yun-Hui Je; Seok-Hoon Yoon; Seik Paik; Seung-Rok Han; Ahreum Woo; Jae-Ho Jeon; Donghyun Lim; Seonmi Lim; Jaewon Choi; Eunjung Kim; et al. (Geosciences Journal, 2026)

Sediment facies regulate organic and shell-derived carbonate carbon storage in the Shinan tidal flats, Korea - Yoon-Seo Kim; Yeo-Bin Park; Ji-Won Park; Eui-Joo Kim; Sang-Pil Lee; Seung-Jun Lee; Do-Hun Ryu; Ji-Su Ko; Jun-Mo Kim; Jae-Hoon Park; Yong-Sik Hong; Sang-Kyoung Lee; et al. (Regional Studies in Marine Science, 2026)

Engineering interfacial compatibility between phenolated lignin and poly(butylene adipate-co-terephthalate) toward sustainable biodegradable plastics - Jae Hoon Lee; Gihyun Kwon; SeungHyeon Song; Mingyo Choi; Seungjun Choi; Kyeongmin Hong; Yong Chae Jung; Jaewon Byun; Yong-Seok Choi; Jeehoon Han (Chemical Engineering Journal, 2026)

GeoGMI: A generative adversarial framework for virtual 89 GHz microwave brightness temperature retrieval from geo-kompsat-2A infrared observations for tropical cyclone monitoring - Kyung-Hoon Han; Suna Jo; Sungwook Hong (Atmospheric Research, 2026)

Doubling frequency of summer cold surges in recent decades and their impact on East Asian extreme precipitation - Kwang-Hee Han; Jee-Hoon Jeong; Sung-Ho Woo; Ho-Young Ku; Hayeon Noh; Baek-Min Kim (Atmospheric Research, 2026)

PODFA: A Raspberry Pi-Based User-Friendly Analyzer Measuring Petal Detachment Force in Flower Abscission Studies - Minsoo Han; Hoon Jung; Yuree Lee (Journal of Plant Biology, 2026)

Evaluation of seasonal variations in energy sources and trophic positions of Calanus sinicus and Euphausia pacifica in the central-eastern Yellow Sea using bulk and compound-specific stable isotope analyses - Jiseung Kang; Yeonjung Lee; Dong Han Choi; Jae Hoon Noh; Howon Lee; Hyung-Ku Kang; Garam Kim; Kongtae Ra; Myung Jin Hyun; Won Seok Yang; JongSeok Won; Bohyung Choi; et al. (Marine Pollution Bulletin, 2026)

Editor's Note to “Inhibiting bacterial biofilm formation by stimulating c-di-GMP regulation using citrus peel extract from Jeju Island” [Sci. Total Environ., 872, (2023), 162180] - Han-Shin Kim; So-Young Ham; Hwa-Soo Ryoo; Hee-Deung Park; Jeong-Hoon Park (Science of The Total Environment, 2026)

Plant life form, biomass allocation, and belowground structure shape depth-dependent soil organic carbon accumulation as blue carbon sources in vegetated tidal flats - Jae-Hoon Park; Yeo-Bin Park; Ji-Won Park; Sang-Pil Lee; Do-Hun Ryu; Seung-Jun Lee; Jun-Mo Kim; Ji-Su Ko; Eui-Joo Kim; Yoon-Seo Kim; Young-Han You (Science of The Total Environment, 2026)

Near-infrared light–responsive implantable module integrated into glaucoma drainage device for controlled antifibrotic drug therapy - Chang Hee Min; Young In Shin; Han Bi Ji; Soo Bin Yoon; Yeonseo Kim; Cho Rim Kim; Jae Hoon Han; Min Ji Kim; Myung Ju Kim; Eun Jung Kwon; Young Kook Kim; Ki Ho Park; et al. (Chemical Engineering Journal, 2026)

Comparison between genomic alterations in mouse, pig, and human through whole-genome sequencing - Geon Hue Bae; Seong Gyu Kwon; Jeong-Woo Choi; Joo Hee Hong; CheolMin Jeon; Areum Cho; JaeEun Shin; Mee Sook Jun; Man-Hoon Han; Seock Hwan Choi; Ji Won Oh (Journal of Genetics, 2026)

Integrative culture-based and 16S rRNA microbiome analysis combined with on-site temperature evaluation to enhance safety management of salt-fermented octopus and clams - Ki Won Lee; Young Hoon Lee; Yun O; Hea Yeon Han; Ga-Hee Ban; Min Suk Rhee; Sun Ae Kim; Tae Jin Cho (Food Control, 2026)

Corrigendum to ‘Food waste shock for reducing methane emissions from sewer pipelines’ - Mohamadali Mohit; Om Prakash; Masoud Makian; Ali Ashraf Joolaei; Xueqing Shi; Jong-Han Lee; Dong-Hoon Kim (Resources, Conservation and Recycling, 2026)

Artificial intelligence‑based quantitative analysis of hepatic fibrosis in carbon tetrachloride-induced mouse model of metabolic dysfunction-associated steatohepatitis - Jin-Hee Lee; Myung-Hwa Yang; Gyeongjin Han; Won Hoon Jung; Myung Ae Bae; Ji-Seok Han; Tae-Sung Koo; Jae-Woo Cho (Toxicological Research, 2026)

Formulation development of basroparib as a first-in-class tankyrase inhibitor using a microprecipitated bulk powder approach - Uk-Il Kim; Ravi Maharjan; Hyo-Kyung Han; Kyungjin Kim; Seong Hoon Jeong (Journal of Pharmaceutical Investigation, 2026)

Anti-melanogenesis and Anti-wrinkle Effects of Novel Peptides Derived from Tenebrio Molitor L. (mealworm) Expressed by Gamma-Irradiation - Hanui Lee; Gyeong Han Jeong; Ji Wan Choi; Tae Hoon Kim; Byung Yeoup Chung; Seung Sik Lee (International Journal of Peptide Research and Therapeutics, 2026)

Volumetric landscape: The mix characteristics and co-agglomeration of 3D space use in compact cities - Yi-Ya Hsu; Hoon Han (Landscape and Urban Planning, 2026)

A feasibility study of a non-aromatic oil as an alternative fuel for its application to jet aviation and rocket-engine fuels - Hee Sun Han; Cheon Hyeon Cho; Yejin Kang; Chae Hoon Sohn (Fuel, 2026)

Diesel exhaust particles attenuate skeletal muscle cell proliferation and induce skeletal muscle atrophy through activation of AMP-activated protein kinase - Yeong Hoon Kang; Hyun Joung Lim; Eunsook Park; Jihye Bang; Hee-Soo Han; Youngyoul Kim; Min Ju Kang; Kyung-Ok Uhm; Hyeon Soo Kim (Molecular & Cellular Toxicology, 2026)

Inhibition of MID1IP1 induces ferroptosis and suppresses c-Myc expression in colorectal cancer cell - Je Joung Oh; Yu Jin Lee; Yeo Jeong Han; Yui Sasaki; Jinbong Park; Woojin Kim; Ji Hoon Jung (Genes & Genomics, 2026)

Biofouling mitigation in cathodic electrochemical filtration via combined sublethal oxidative stress and electrostatic repulsion - Jeong Hoon Lee; Han-Shin Kim; Eun-Tae Yun; So-Young Ham; Peng-Fei Sun; Hwa-Soo Ryoo; Hee-Deung Park (Water Research, 2026)

Food waste shock for reducing methane emissions from sewer pipelines - Mohamadali Mohit; Om Prakash; Masoud Makian; Ali Ashraf Joolaei; Xueqing Shi; Jong-Han Lee; Dong-Hoon Kim (Resources, Conservation and Recycling, 2026)

Spatiotemporal variations of dissolved organic matter in coastal groundwater and controlling biogeochemical factors in tidal flats of Incheon, on the west coast of Korea - Hyung-Mi Cho; Gayeon Kim; Minjun Kim; Heejun Han; Jeonghyun Kim; Tae-Hoon Kim; Hyun Je Park (Regional Studies in Marine Science, 2026)

Primary succession of vegetation on large river bars affected by floods: Key factors for successful river restoration - Jae-Hoon Park; Ji-Won Park; Yeo-Bin Park; Eui-Joo Kim; Young-Han You (Ecological Engineering, 2026)

γ-ray induced microstructure modulation for enhanced output performance of polyimide-based piezoelectric composites - Dong Yeol Hyeon; Gyoung-Ja Lee; Hyeon Jun Park; Dong Won Jeon; Han Uk Lee; Sung Beom Cho; Jaehun An; Nagamalleswara Rao Alluri; Young Hoon Jung; Changyeon Baek; HakSu Jang; SungHoon Kim; et al. (Chemical Engineering Journal, 2026)

Thermophilic composting of dewatered sewage sludge under subzero temperatures using a full-scale pre-fermentation reactor: A 10-day valorisation strategy for year-round operation - Huitae Min; Hyejin Ko; Sang Hoon Jung; Ji Yeon Han; Chi Won Lee; Seungchan An; Young-Joo Kim; Taejung Kim; Jungyeob Ham; Wonbae Kim; Young-Tae Park (Journal of Environmental Management, 2025)

β–phase polymer-driven enhanced powder flowability and microstructure uniformity for stable and fast dry-processed electrode - Min Jang; Hyeongseok Shim; Sijeong Park; Hyeju Shin; Jeong-Rae Jo; Wooyoung Jin; Hyungyeon Cha; Jung Hoon Kim; Joong Tark Han; Gyujin Song; Sinho Choi (Chemical Engineering Journal, 2025)

Upcycling polycrystalline silicon from waste solar cells for thermally conductive epoxy composites: Anisotropic crystallite growth and tailored microstructure via heat treatment - Yoon Hye Han; Kyung Hoon Min; Hye In Kang; Yu Min Lim; Haolin Wang; Hyunseong Shin; Sang Eun Shim (Chemical Engineering Journal, 2025)

Identification of Biomarkers Related to the Pathogenesis and Prognosis of Pediatric Moyamoya Disease Via Cerebrospinal Fluid Proteomics - Youngbo Shim; Seung Ah Choi; Kisoon Dan; Eun Jung Koh; Saehim Ha; Ji Hoon Phi; Joo Whan Kim; Dohyun Han; Seung-Ki Kim (Translational Stroke Research, 2025)

Radixin in the nucleus accumbens core modulates amphetamine-induced locomotor activity based on context association - Wen Ting Cai; Myung Ji Kwak; Joonyeup Han; Haeun Rim; Lars Björn Riecken; Helen Morrison; Wha Young Kim; Jeong-Hoon Kim (Psychopharmacology, 2025)

First Assessment of Coccolithophore-Driven Carbonate Flux in the Ulleung Basin, East Sea (Sea of Japan) - Sung Min An; Dong Han Choi; Young-Il Kim; Young Suk Chang; Jae Hoon Noh (Ocean Science Journal, 2025)

Lung neoplasm development in a mouse model exposed to fine particulate matter in Korea - Hyunseung Oh; Yoon Jeong Nam; Jin Young Choi; Hyejin Lee; Hong Lee; Yu-Seon Lee; Yoon Hee Park; Su A. Park; Hayan Park; Jaeyoung Kim; Sang Hoon Jeong; Ju-Han Lee (Molecular & Cellular Toxicology, 2025)

Generation of NOD SCID mice with near-complete deletions of Il2rg and Prkdc for human cancer and HSC engraftment - You-Min Kim; Hee Ju Na; Do Hee Kwon; Jae Hoon Lee; Bo Min Park; Subin Lee; Tae Wook Nam; Mi Yeon Park; Sun Ha Park; Sung Joo Kim; Bongkum Choi; Han-Woong Lee (Transgenic Research, 2025)
Immunodeficient mouse models are invaluable tools for preclinical research, particularly for cancer therapies and studies of the human immune system. Notably, strains with combined Prkdc (scid) and Il2rg (null) mutations—such as NOG and NSG mice— are widely used due to their profound immunodeficiency, allowing efficient engraftment of various human cells. However, these models were generated by disrupting the Il2rg gene through replacement with a neomycin resistance (Neo) cassette in embryonic stem cells. Incomplete excision of this cassette can inadvertently alter the expression of neighboring genes, thereby introducing potential confounding variables. In addition, they may still express mutant mRNAs that escape nonsense-mediated decay (NMD) and/or produce truncated proteins with residual activity, potentially compromising the interpretation of experimental outcomes. To address this, we developed the N2G mouse strain (NOD-2-Genes KO) where almost all genomic loci of both Prkdc and Il2rg genes are deleted via CRISPR/Cas9 genome editing. N2G mice exhibited tumor growth comparable to NOG mice following the transplantation with several human cancer cell lines. Moreover, human CD34 + cord blood (CB) cells engrafted into N2G mice showed robust reconstitution of human immune cells, especially T cells in peripheral blood, spleen and bone marrow, compared to NSG mice. These results suggest that N2G mice, lacking residual mutant mRNA and the exogenous Neo resistant gene, offer an advanced model for preclinical studies.

Seasonal interplay of water mass mixing and nutrient dynamics in an Arctic fjord: a case study of Kongsfjorden, Svalbard - Hyebin Kim; Dukki Han; Sang Rul Park; Tae-Hoon Kim (Ocean Science, 2025)
This study examined seasonal variations in water mass structure and nutrient dynamics in Kongsfjorden, a high Arctic fjord where water mass composition varies seasonally due to mixing among Atlantic Water, Polar Surface Water, and glacial meltwater. In spring, the dominance of Modified Atlantic Water (MAW) facilitated active vertical mixing, leading to relatively high, uniform nutrient concentrations throughout the water column. In summer, the enhanced influence of glacial meltwater and warmer Polar Surface Waters (PSWw) resulted in strong surface stratification and significant nutrient depletion in the upper layer. To disentangle the effects of physical mixing from biological consumption, theoretical nutrient concentrations were calculated based on a four-component water mass mixing model. The positive differences between theoretical and observed concentrations (ΔNutrient) were indicative of significant biological uptake, which accounted for substantial nutrient reductions in observed surface concentrations from spring to summer: approximately 69 ± 18 % for NOx (sum of nitrate and nitrite; NO3- + NO2-), 74 ± 15 % for phosphate, and 47 ± 18 % for silicate. Crucially, ΔNutrient values served as a “biogeochemical memory”, reflecting the cumulative net biological consumption since the spring bloom rather than just instantaneous phytoplankton biomass. These biological processes also altered nutrient stoichiometry, as reflected by an increase in the surface dissolved inorganic nitrogen to phosphorus (DIN/DIP) ratio (DIN = NO2? + NO3- + NH4+; DIP = PO43-) from 15.0 in spring to 18.8 in summer, indicating a shift in nutrient limitation patterns. Consequently, summer surface waters transitioned toward potential co-limitation, with concentrations of phosphate (∼ 0.13 ± 0.07 µM) and silicate (∼ 1.66 ± 0.39 µM) approaching their respective limitation thresholds. These findings highlight a clear seasonal transition from a physically controlled, nutrient-replete spring to a biologically regulated, nutrient-limited summer. This understanding is crucial for predicting how Arctic fjord ecosystems, and their primary productivity, will respond to ongoing Atlantification and increased freshwater input under climate change.

Seismogenesis in the brittle–plastic transition zone of the Yecheon shear zone, South Korea - Jae Hoon Kim; Jin-Han Ree (Journal of Structural Geology, 2025)

Enhancement of syngas production via plastic gasification in low-concentration CO2 by using spent lithium-ion batteries-derived black mass - Dong-Wan Cho; Hyeop-Jo Han; Jae-Hoon Hwang; Yongtae Ahn; Hyeonjung Yu (Journal of Environmental Management, 2025)

Association Between ABCG2 Polymorphism and Statin-Induced Adverse Events: A Meta-Analysis - Da Hoon Lee; Hae Ji Shin; Beom Yoon; Han Wool Kim; Hyeon Woo Jo; Hee Jung Kim; Woorim Kim (Cardiovascular Toxicology, 2025)

Ship-hull mediated introduction risk of Colaconema formosanum: barnacle-associated dispersal and ecophysiological potential for coastal establishment - Ju-Hyoung Kim; Ye Rim Kim; Min Gui Jung; Eun Ju Kang; Kyoungsoon Shin; Bonggil Hyun; Jung-Hoon Kang; Seung Ho Baek; Il-Nam Kim; Jong Won Han; Jee Eun Lee; Hyung Woo Lee (Biological Invasions, 2025)

Microstructure of garnet in calc-silicate rocks from Cheongsong, South Korea: Effects of fluid and deformation - Seokyoung Han; Sejin Jung; Ji-Hoon Kang; Haemyeong Jung (Journal of Structural Geology, 2025)

Development of amine-functionalized cerium dioxide for direct air capture of CO2: A chemical adsorption study - Xuelong Zhuang; Jae Yeon Hwang; Mi Yeong Ko; Sung Woo Han; Edoardo Magnone; Jung Hoon Park (Journal of Environmental Chemical Engineering, 2025)

Scalable and sustainable epoxide-functionalized polyethyleneimine/silica adsorbent for carbon dioxide capture from flue gases - Younghun Kim; Dae Hoon Park; Gunhee Lee; Jungho Hwang; Bangwoo Han (Chemical Engineering Journal, 2025)

Biogas production from bioplastics: Pretreatment strength assessment through repeated batch tests under mesophilic and thermophilic conditions - Ali Ashraf Joolaei; Om Prakash; Masoud Makian; Mohamad Ali Mohit; Sungwon Kang; Seongwon Im; Jong-Han Lee; Dong-Hoon Kim (Biomass and Bioenergy, 2025)

Establishment of Immune-Evasive iPSCs from PBMCs Using B2M Knockout and CD47/HLA-E Overexpression - Cha Yeon Kim; Cholong Jeong; Yeon-Ju Jeong; Young Hoon Sung; Youngjin Han; Changmo Hwang (Tissue Engineering and Regenerative Medicine, 2025)

Species Diversity and Net Primary Productivity of Plant Communities in the Coastal Ecosystems of Southwestern Korea - Ji-Won Park; Eui-Joo Kim; Jae-Hoon Park; Yeo-Bin Park; Jung-Min Lee; Seung-Jun Lee; Young-Han You (Journal of Plant Biology, 2025)

Mapping the vertical city: AI-driven analysis of volumetric urban space use - Yi-Ya Hsu; Hoon Han (Sustainable Cities and Society, 2025)

Nociceptive effects and gene alterations of CMIT/MIT mixture in zebrafish embryos and larvae - Hong Lee; Yeonhwa Kim; Yuji Cho; Eun Jung Jeon; Sang Hoon Jeong; Ju-Han Lee; Suhyun Kim (Journal of Hazardous Materials, 2025)

OTOP3 functions as an oncogenic regulator of ferroptosis-mediated colorectal cancer progression - Yu Jin Lee; Yeo Jeong Han; Je Joung Oh; Seung-Young Kim; Jaehoon Cho; Ji Hoon Jung (Genes & Genomics, 2025)

Assessment of ship hull-attached marine diatoms: species composition and reattachment - Jaeyeong Park; Buhari Lawan Muhammad; Taehee Kim; Quynh Thi Nhu Bui; Han-Sol Kim; Kyoungsoon Shin; Bonggil Hyun; Jung-Hoon Kang; Jang-Seu Ki (Marine Pollution Bulletin, 2025)

Temporal variations in pore water and gas geochemistry in shallow marine sediments over four years following offshore CO2 injection in Yeongil Bay, South Korea - Myong-Ho Park; Ji-Hoon Kim; Moohee Kang; Se Won Chang; Han Na Na; Jin Hur; Meilian Chen; Young Jae Shinn; Yi Kyun Kwon; Jong-Hwa Chun; Yuri Kim; Byoung-Yeop Kim (Science of The Total Environment, 2025)

Facile strategy for high-efficiency purification and regeneration of graphite anodes from spent lithium-ion batteries - San-Seong Cho; Sang-Hoon Park; Joonhee Kang; Seung-Min Lee; Junhyuck Park; Sinho Choi; Hyun-Kyung Kim; Ji-Eun Hong; Yu-Jin Han (Chemical Engineering Journal, 2025)

Improved estimation of new particle formation rate for air quality model in a polluted region of South Korea - Yusin Kim; Sangdeok Shim; Seogju Cho; Seong Soo Yum; Chul Han Song; Sung Hoon Park (Atmospheric Environment, 2025)

Recent Advances in Three-Dimensional In Vitro Models for Studies of Liver Fibrosis - Kyun Yoo Chi; Gyeongmin Kim; Jeong Sang Son; Jiyou Han; Jong-Hoon Kim (Tissue Engineering and Regenerative Medicine, 2025)

Spatial-temporal modeling for urban climate: Enhancing energy prediction with global temporal convolutional attention networks - Yang Lin; Hoon Han; Christopher Pettit (Urban Climate, 2025)

Erratum: Effects of Zooplankton Extracts on the Production of Paralytic Shellfish Toxins by Gymnodinium catenatum and Alexandrium pacificum - Jae Yeon Park; Dong Han Choi; Na Yeong Kim; Myung Jin Hyun; Young-Eun Kim; Jae-Hoon Noh; Jung-Rae Rho; Bum Soo Park; Seongjin Hong; Sea-Yong Kim; Mungi Kim; Jeonghoon Han; et al. (Ocean Science Journal, 2025)

Improved method for estimating trophic position of the coastal blooming moon jellyfish aurelia coerulea: considering large carbon trophic discrimination factors and diet contributions - Heejoong Kim; Dokyun Kim; Bohyung Choi; Young-Ok Kim; Chang-Hoon Han; Jinho Chae; Eun-Ji Won; Kyung-Hoon Shin (Marine Biology, 2025)

Changes in regulatory requirements for potency testing of snake antivenom in Korea - Wonjong Lee; Hyun Jeong Kim; Yu Jeong Oh; Su Kyoung Seong; Young Hoon Kim; Youngju Choi; Sang-Mi Park; Kiwon Han; Chan Woong Choi (Toxicon, 2025)

Stability conditions of clathrate hydrates formed with liquid or gas CO₂ using deep seawater collected from the East Sea of Korea toward ocean storage - Joonwoo Seo; Siyoon Jeong; Hyunsoo Han; Sangmin Jeon; Jeong-Hoon Sa (Journal of Environmental Chemical Engineering, 2025)

Fluorinated SO2-based inorganic electrolytes for enhanced electrochemical performance in Li-metal anodes - Jiwhan Lee; Seong Hoon Choi; Seung Do Mun; Kyuju Kwak; Samuel Seo; Kyoung Han Ryu; Hansu Kim (Chemical Engineering Journal, 2025)

Spatial and Temporal Variation of Synechococcus Abundance and Diversity in the Yellow Sea - Jongseok Won; Myungjin Hyun; Wonseok Yang; Howon Lee; Yeonjung Lee; Seok Lee; Kongtae Ra; Hee Cheol Yang; Jae Hoon Noh; Dong Han Choi (Ocean Science Journal, 2025)

Corrigendum to ‘Deciphering the toxicity of polyhexamethylene guanidine phosphate in lung carcinogenesis: Mutational profiles and molecular mechanisms’ [Chemosphere Volume 368 (2024) 143785] - Hong Lee; Sang Hoon Jeong; Yong-Wook Baek; Hyejin Lee; Jason K. Sa; Ji Yoon Lee; Yu-Seon Lee; Yoon Jeong Nam; Jaeyoung Kim; Jonghoon Kim; Jin Young Choi; Su A. Park; et al. (Chemosphere, 2025)

Reactive metal–support interaction of In2O3/crystalline carbon hybrid support for highly durable and efficient oxygen reduction reaction electrocatalyst - Seung Min Woo; Han Seul Kim; Pil Ju Youn; Kyung Rog Lee; Gyu Mi Kang; Sang-Hoon You; Kug-Seung Lee; Yong-Tae Kim; Seung-Ho Yu; Jeong Hwan Han; Sung Jong Yoo; Il-Kyu Park (Chemical Engineering Journal, 2025)

Gallibacterium faecale sp. nov., Isolated from Dairy Cow Feces - Seoung Woo Ryu; Jeong Chan Moon; Byeong Seob Oh; Seung Yeob Yu; Jeong Eun Bak; Eun Seo Heo; Seung-Hwan Park; Se Won Kang; Jiyoung Lee; Mi-Kyung Lee; Mooyoung Jung; Yo Han Choi; et al. (Current Microbiology, 2025)

-Spatiotemporal dynamics of nutrients and organic carbon in coastal seawater off Jeju Island: Effects of submarine groundwater discharge (SGD) and geomorphic settings - Heejun Han; Tae-Hoon Kim; Hyung-Mi Cho; Guebuem Kim; Hyeong Kyu Kwon; Minji Lee (Regional Studies in Marine Science, 2025)

Complete chloroplast genomes of three Polygala species and indel marker development for identification of authentic polygalae radix (Polygala tenuifolia) - Sumin Jeong; Jong Won Han; Yeseul Kim; Eunjeong Bak; Kyung Ho Ma; Jeong Hoon Lee; Jin Tae Jung; Inkyu Park (Genes & Genomics, 2025)

Capturing the distance decay effect of amenities on housing price using explainable artificial intelligence - Hojun Lee; Hoon Han; Chris Pettit (Applied Geography, 2025)

The photosynthetic uptake of inorganic carbon from Pyropia seaweed aquaculture beds: Scaling up population-level estimations - Ju-Hyoung Kim; Hanbi Moon; Mi-Jung Han; Ji Eun Jung; Na Young Lee; Jin Woo Kang; Ji Chul Oh; Geun-Ha Park; Seon-Eun Lee; Myoung Hoon Lee; Chae-Un Park; Ho-Sung Yoon; et al. (Aquaculture, 2024)

Optimized antifouling γ-Al2O3/α-Al2O3 nanofiltration composite membrane for lignin recovery from wastewater - Xuelong Zhuang; Sung Woo Han; Min Chang Shin; Jae Yeon Hwang; Jung Hoon Park (Water Research, 2024)

Decadal trends and predictive insights into aquatic ecosystem health in the Namhan River, South Korea: Longitudinal analysis of hydro-environmental factors and stream health indices (2008–2022) - Hemie Cho; Pamela Sofia Fabian; Sang-Hoon Lee; Kyung-A You; Hyun-Han Kwon (Environmental Pollution, 2024)

Development and field deployment validation of a low-cost and high-precision displacement sensing system by fusing millimeter-wave radar and accelerometer - Zhanxiong Ma; Kyuwon Han; Jaemook Choi; Jigu Lee; Ohjun Kwon; Hoon Sohn; Jingxiao Liu; Doyun Hwang; Jatin Aggarwal; Haeyoung Noh; Enjian Cai; Yi Zhang (Engineering Structures, 2024)

Cellular automata modelling to simulate patterns of urban growth for Nusantara: Indonesia’s new capital - Dody Arfiansyah; Scott Hawken; Sisi Zlatanova; Hoon Han (Spatial Information Research, 2024)
This paper uses cellular automata (CA) modelling to simulate possible patterns of urban growth for Nusantara–Indonesia’s new capital. The modelling uses criteria such as projected population growth and planned development stages and a range of relevant factors that influence urban development. Further the study simulates the possible impact of future urban growth on key biodiversity areas (KBAs). Two scenarios were modelled to simulate urban growth patterns–(1) the nature sensitive city and (2) the Indonesian government’s current plan. Results of the scenario-based CA modelling demonstrate that scenario 1 offers a more sustainable and liveable approach to urban growth, despite its larger land footprint. This is achieved by preserving protected and key biodiversity areas, which are essential for the long-term well-being and resilience of the environment. While scenario 2 is more land-efficient, it presents a possible risk to the overall ecological integrity and liveability of the metropolis by impinging into key biodiversity areas. The study’s cellular automata approach and methodology can be employed for urban planning and biodiversity impact assessment in similar contexts of new city development.

Impacts of Typhoon Bavi on Prokaryotic Communities in the Yellow Sea - Wonseok Yang; Myung Jin Hyun; Jae Hoon Noh; Yeonjung Lee; JongSeok Won; Howon Lee; Kongtae Ra; Dong Han Choi (Ocean Science Journal, 2024)

Effects of Zooplankton Extracts on the Production of Paralytic Shellfish Toxins by Gymnodinium catenatum and Alexandrium pacificum - Jae Yeon Park; Dong Han Choi; Na Yeong Kim; Myung Jin Hyun; Young-Eun Kim; Jae-Hoon Noh; Jung-Rae Rho; Bum Soo Park; Seongjin Hong; Sea-Yong Kim; Mungi Kim; Jeonghoon Han; et al. (Ocean Science Journal, 2024)

Comprehensive analysis of somatic mutations and structural variations in domestic pig - Seong Gyu Kwon; Geon Hue Bae; Joo Hee Hong; Jeong-Woo Choi; June Hyug Choi; Nam Seop Lim; CheolMin Jeon; Nanda Maya Mali; Mee Sook Jun; JaeEun Shin; JinSoo Kim; Eun-Seok Cho; et al. (Mammalian Genome, 2024)

Erratum: Characteristics of Succession and Plant Biodiversity of Montane Grasslands in the Republic of Korea - Eui-Joo Kim; Ji-Won Park; Young-Han You; Jae Hoon Park (Journal of Plant Biology, 2024)

Deciphering the toxicity of polyhexamethylene guanidine phosphate in lung carcinogenesis: Mutational profiles and molecular mechanisms - Hong Lee; Sang Hoon Jeong; Yong-Wook Baek; Hyejin Lee; Jason K. Sa; Ji Yoon Lee; Yu-Seon Lee; Yoon Jeong Nam; Jaeyoung Kim; Jonghoon Kim; Jin Young Choi; Su A. Park; et al. (Chemosphere, 2024)

Reduction of aflatoxins and ochratoxin A by addition of commercial Koji during fermentation of the Korean traditional soybean paste, Doenjang - So Young Woo; Fei Tian; Sang Yoo Lee; Su Been Park; Kap-Hoon Han; Hye-Young Kim; Hyang Sook Chun (Food Control, 2024)

Boosting the active sites of Cu/Ce0.8Zr0.2O2 catalysts through tailored precipitation method - Seon-Yong Ahn; Jong-Hoon Han; Hyun-Seog Roh (Chemical Engineering Journal, 2024)

25-Hydroxycholesterol induces oxidative stress, leading to apoptosis and ferroptosis in extravillous trophoblasts - Ki Mo Lee; Tae Hoon Kim; Eui-Jeong Noh; Jae Won Han; Jong-Seok Kim; Sung Ki Lee (Chemico-Biological Interactions, 2024)

Tectonic evolution of the eastern margin of the Northern South Yellow Sea Basin in the Yellow Sea since the Late Cretaceous - Seonghoon Moon; Han-Joon Kim; Sookwan Kim; Jongha Hwang; Chung-ho Kim; Su-hwan Lee; Sang-Hoon Lee; Gwang Hoon Lee (Journal of Asian Earth Sciences, 2024)

High-Speed Clearing and High-Resolution Staining for Analysis of Various Markers for Neurons and Vessels - Jung Min Park; Seock Hwan Choi; Eun-Shil Lee; Sang-Il Gum; Sungkuk Hong; Dong Sun Kim; Man-Hoon Han; Soung-Hoon Lee; Ji Won Oh (Tissue Engineering and Regenerative Medicine, 2024)

Characteristics of Succession and Plant Biodiversity of Montane Grasslands in the Republic of Korea - Eui-Joo Kim; Ji-Won Park; Young-Han You; Jae Hoon Park (Journal of Plant Biology, 2024)

Layered silicate nanoparticles as a non-injectable drug delivery system for biomacromolecules - Jae Geun Song; Sang Hoon Lee; Rajiv Bajracharya; Nonye Linda Ifekpolugo; Gyu-Lin Kim; Seong Jin Park; Seong Hoon Jeong; Chang Hoon Lee; Hyo-Kyung Han (Journal of Pharmaceutical Investigation, 2024)

Green process for Polyurethane: From CO2 to isocyanate - Jung Ae Lim; Young-Woo You; Seung Kwon Kang; Jongseon Rho; Suyeon Yeo; Seulgi Han; Mintaek Im; Un Young Kim; Min-Chul Kim; Tae-Sun Chang; Ji Hoon Park; Jinjoo An; et al. (Chemical Engineering Journal, 2024)

Eggshell membrane as a natural food-grade scaffold for cultured meat - Si Won Jang; Jae Ho Han; Ye Rim Kim; Hoon Jang; Kwan Seob Shim; Hyun Woo Choi (Innovative Food Science & Emerging Technologies, 2024)

Thermodynamic and exergy assessment of a biomass oxy-fuel combustion with supercritical carbon dioxide cycle under various recycle flue gas conditions - Jester Lih Jie Ling; Han Saem Park; Ha Eun Lee; Bhanupratap S. Solanki; See Hoon Lee (Journal of Cleaner Production, 2024)

Performance and techno-economic evaluation of a high-efficiency electrospray cyclone - Jun Su Park; Dae-Gyun Lee; Kang-San Lee; Jin-Han Kim; Jung Hoon Yoo; Hang Joo Shin; Young-Chan Choi; Young-joo Lee; YoungMin Woo; Meehye Lee; Jong Won Choi (Journal of Environmental Chemical Engineering, 2024)

A climate change risk assessment in aquaculture in Korea - Moo-Jin Kim; In-Seong Han; Joon-Soo Lee; Do-Hoon Kim (Climatic Change, 2024)

Deformation-induced right-side-up pseudo-stratigraphy of the early Paleozoic Joseon Supergroup in the southeastern Danyang area, South Korea - Tae-Hoon Uhmb; Jin-Han Ree; Hyeong Soo Kim (Geosciences Journal, 2024)

Macroalgal eukaryotic microbiome composition indicates novel phylogenetic diversity and broad host spectrum of oomycete pathogens - Natalia Timanikova; Kyle Fletcher; Jon‐Wong Han; Pieter van West; Steve Woodward; Gwang‐Hoon Kim; Frithjof C. Küpper; Marius Wenzel (Environmental Microbiology, 2024)
Seaweeds are important components of marine ecosystems with emerging potential in aquaculture and as sources of biofuel, food products and pharmacological compounds. However, an increasingly recognised threat to natural and industrial seaweed populations is infection with parasitic single‐celled eukaryotes from the relatively understudied oomycete lineage. Here we examine the eukaryomes of diverse brown, red and green marine macroalgae collected from polar (Baffin Island), cold‐temperate (Falkland Islands) and tropical (Ascension Island) locations, with a focus on oomycete and closely related diatom taxa. Using 18S rRNA gene amplicon sequencing, we show unexpected genetic and taxonomic diversity of the eukaryomes, a strong broad‐brush association between eukaryome composition and geographic location, and some evidence of association between eukaryome structure and macroalgal phylogenetic relationships (phylosymbiosis). However, the oomycete fraction of the eukaryome showed disparate patterns of diversity and structure, highlighting much weaker association with geography and no evidence of phylosymbiosis. We present several novel haplotypes of the most common oomycete Eurychasma dicksonii and report for the first time a cosmopolitan distribution and absence of host specificity of this important pathogen. This indicates rich diversity in macroalgal oomycete pathogens and highlights that these pathogens may be generalist and highly adaptable to diverse environmental conditions.

The effect of exopolysaccharides from EMS-induced Porphyridium cruentum mutant on human epidermal and dermal layers - Sang-Il Han; Young Mok Heo; Min Seo Jeon; Seoyeon Kyung; Seunghyun Kang; Soon-Jae Kwon; Jai Hyunk Ryu; Jae Hoon Kim; Joon-Woo Ahn (Frontiers in Marine Science, 2024)
Introduction Microalgae biotechnology utilizes species like Porphyridium cruentum for their valuable phycobiliproteins and exopolysaccharides, which have potential industrial applications and health benefits, particularly in skin condition improvement. Methods A mutant of P. cruentum LIMS-PS-1061 was developed through ethyl methanesulfonate mutagenesis and subsequent colony screening to study changes in its biomass production and pigment composition under different lighting conditions. Results and discussion The mutant exhibited a 33.9% increase in dry weight under white light compared to the wild type. Despite maintaining the total pigment content, specific components changed significantly: chlorophyll content decreased 2.20- and 3.61-fold under white and blue light respectively, while phycobiliproteins increased 1.59- and 1.23-fold under the same conditions. These alterations suggest a compensatory mechanism for maintaining photosynthetic capacity. Furthermore, the exopolysaccharides of P. cruentum upregulated genes related to skin moisturization, barrier enhancement, and elasticity, and promoted wound healing through fibroblast migration. This supports the proposed mechanism of action for P. cruentum’s exopolysaccharides in improving human skin conditions by integrating the effects of aquaporin 3, filaggrin, involucrin, loricrin, elastin, and fibrillin-1.

Benzyl-methylbenzyl-benzene: Improving hydrogen storage and release performance of dibenzyltoluene based liquid organic hydrogen carrier - Kwanyong Jeong; Hyunwoo Yook; So Hyeon Lee; Hwa Jin Han; Yunkyeong Jung; Seulgi Han; So Yeon Shin; Myungho Choi; Sunil Kwon; Jin Hee Lee; Sang-Joon Kim; Soo Min Kim; et al. (Chemical Engineering Journal, 2024)

An electro-ferroptotic nanoammunition enables image-guided, spatiotemporally controlled cancer ferroptosis induction via irreversible electroporation - Jun-Hyeok Han; Hee Seung Seo; Jiyoung Lee; Zheng Chen; Qiyue Wang; Yun Young Lee; Na Kyeong Lee; Jeon Min Kang; Song Hee Kim; Hwichan Hong; Jung-Hoon Park; Yuanzhe Piao; et al. (Chemical Engineering Journal, 2024)

Organic clay-based fast dissolving microneedles for efficient transdermal delivery of therapeutic proteins - Jae Geun Song; Sang Hoon Lee; Hyo-Kyung Han (Journal of Pharmaceutical Investigation, 2024)

Tyrosinase inhibitors isolated from Iris bungei collected in Mongolia - Gyeong Han Jeong; Tae Hoon Kim (Phytochemistry Letters, 2024)

Targeted Metabolomic Biomarkers for Stroke Subtyping - Eung-Joon Lee; Da Jung Kim; Dong-Wan Kang; Wookjin Yang; Han-Yeong Jeong; Jeong-Min Kim; Sang-Bae Ko; Seung-Hoon Lee; Byung-Woo Yoon; Joo-Youn Cho; Keun-Hwa Jung (Translational Stroke Research, 2024)

Advancements in Human Embryonic Stem Cell Research: Clinical Applications and Ethical Issues - Soo Jin Park; Yoon Young Kim; Ji Yeon Han; Sung Woo Kim; Hoon Kim; Seung-Yup Ku (Tissue Engineering and Regenerative Medicine, 2024)
Background: The development and use of human embryonic stem cells (hESCs) in regenerative medicine have been revolutionary, offering significant advancements in treating various diseases. These pluripotent cells, derived from early human embryos, are central to modern biomedical research. However, their application is mired in ethical and regulatory complexities related to the use of human embryos. Method: This review utilized key databases such as ClinicalTrials.gov, EU Clinical Trials Register, PubMed, and Google Scholar to gather recent clinical trials and studies involving hESCs. The focus was on their clinical application in regenerative medicine, emphasizing clinical trials and research directly involving hESCs. Results: Preclinical studies and clinical trials in various areas like ophthalmology, neurology, endocrinology, and reproductive medicine have demonstrated the versatility of hESCs in regenerative medicine. These studies underscore the potential of hESCs in treating a wide array of conditions. However, the field faces ethical and regulatory challenges, with significant variations in policies and perspectives across different countries. Conclusion: The potential of hESCs in regenerative medicine is immense, offering new avenues for treating previously incurable diseases. However, navigating the ethical, legal, and regulatory landscapes is crucial for the continued advancement and responsible application of hESC research in the medical field. Considering both scientific potential and ethical implications, a balanced approach is essential for successfully integrating hESCs into clinical practice.

The complement factor H-related protein-5 (CFHR5) exacerbates pathological bone formation in ankylosing spondylitis - Ji-Hyun Lee; Seung Hoon Lee; Chanhyeok Jeon; Jinil Han; Sang-Hyon Kim; Jeehee Youn; Ye-Soo Park; Tae-Jong Kim; Jong-Seo Kim; Sungsin Jo; Tae-Hwan Kim; Chang-Nam Son (Journal of Molecular Medicine, 2024)

Identifying the external N and Hg inputs to the estuary ecosystem based on the triple isotopic information (δ15NNO3, Δ17ONO3 and δ18ONO3) - Haryun Kim; Hye Seon Kim; Jihee Kim; Dongwoo Yang; Kitack Lee; Kitae Kim; Giyoung Ock; Hyung-Geun Park; Rebecca S. Robinson; Min-Seob Kim; Geun-Ha Park; Ju-Hyoung Kim; et al. (Marine Pollution Bulletin, 2024)

High-performance interfacial water evaporation of black TiO2-x with high-concentration bulk oxygen vacancies - Myeongjun Ji; Jeong Hyun Kim; Hee Yeon Jeon; Seungheon Han; Dong Hoon Lee; Young-In Lee (Chemical Engineering Journal, 2024)

Optimizing electroactive membrane performance for microalgae harvesting: A response surface methodology study of membrane formulation and operating parameters for electro filtration - Azeem Mushtaq; Hoon Cho; Asma Batool; Muhammad Tahir Fazal; Muhammad Aslam; Muhammad Saif UR. Rehman; Jason Chun-Ho Lam; Jong-In Han (Chemosphere, 2024)

The effect of weathering on cohesion in granitic fault rocks: A case study from the Yeongdeok Fault, South Korea - Jae Hoon Kim; Jin-Han Ree; Wataru Tanikawa; Hee-Cheol Kang (Journal of Structural Geology, 2024)

High C2H6/C2H4 selectivity via incorporation of dense methyl groups into a stable Zr-based MOF with cavity-like pores - Wanje Park; Tea-Hoon Kim; Kwang Hyun Oh; Hyug Hee Han; Yujin Choi; Kijun Kim; Youn-Sang Bae (Chemical Engineering Journal, 2024)

Monodentate binding of zwitterionic ligands for boosting photocatalytic H2 production of perovskite nanocrystals - Sung Hoon Noh; Kyeong Ho Lee; Han Sol Yang; Jaemin Jung; Eui Hyun Suh; Jong Gyu Oh; Ungyu Paik; Seul Chan Park; Jaeyoung Jang (Chemical Engineering Journal, 2024)

Effects of Cetrorelix on Ovary and Endometrium Prior to Anti-PD-L1 Antibody in Murine Model - Soo Jin Park; Yoon Young Kim; Wonhyoung Park; Sunwoo Park; Ji Yeon Han; Sung Woo Kim; Hoon Kim; Seung-Yup Ku (Tissue Engineering and Regenerative Medicine, 2024)

Application of Cartilage Extracellular Matrix to Enhance Therapeutic Efficacy of Methotrexate - Jeong-Woo Seo; Sung-Han Jo; Seon-Hwa Kim; Byeong-Hoon Choi; Hongsik Cho; James J. Yoo; Sang-Hyug Park (Tissue Engineering and Regenerative Medicine, 2024)

Development of Biological Risk Assessment Protocols for Evaluating the Risks of In-Water Cleaning of Hull-Fouling Organisms - Bonggil Hyun; Pung-Guk Jang; Min-Chul Jang; Jung-Hoon Kang; Ju-Hyoung Kim; Jang-Seu Ki; Dong Han Choi; Ok Hwan Yu; Jin-Young Seo; Woo-Jin Lee; Kyoungsoon Shin (Journal of Marine Science and Engineering, 2024)
Herein, we evaluate the scientific basis for managing hull fouling of ships entering Korean ports, diagnose biological risks that may occur when in-water cleaning (IWC) systems remove hull fouling, and present a protocol for evaluating these risks (the Korean Infection Modes and Effects Analysis; K-IMEA). Protocol development included the selection of core elements and scenario design for IWC and the evaluation of regrowth experiments. The K-IMEA index was designed by considering the inoculation pathway of attaching organisms in all processes to ships that enter a port for in-water cleaning. A number of risk indices were defined: R1—Introduction/Establishment of alien species before in-water cleaning; R2—Establishment of alien species escaped during in-water cleaning; R3—Introduction/Establishment of alien species after in-water cleaning; and R4—Establishment of alien species in effluent water. K-IMEA regrowth experiments (R2 and R4) using the in-water cleaning effluent showed that the attachment and regrowth of prokaryotes, microalgae, and macroalgae were successfully detected. In particular, prokaryotes were observed in samples filtered through a 5 μm mesh of the in-water cleaning effluent, even at a low fouling rating (Levels 1–2). These experiments suggest a necessity to consider a secondary treatment method in addition to the primary filtration method for the treatment of in-water cleaning effluents.

Isolation of a quorum quenching bacterium effective to various acyl-homoserine lactones: Its quorum quenching mechanism and application to a membrane bioreactor - Soyoung Ham; Hwa-Soo Ryoo; Yongsun Jang; Sang-Hoon Lee; Ji-Yoon Lee; Han-Shin Kim; Jeong-Hoon Lee; Hee-Deung Park (Chemosphere, 2024)

Achieving ultrasensitivity and high breathability in biodegradable piezoresistive electronic skins - Mohammad Zarei; Jung Hoon Kim; Joong Tark Han; Seung Goo Lee (Chemical Engineering Journal, 2024)

Preliminary Investigation on Efficacy and Safety of Substance P-Coated Stent for Promoting Re-Endothelialization: A Porcine Coronary Artery Restenosis Model - Dae Sung Park; Seok Oh; Yu Jeong Jin; Mi Hyang Na; Munki Kim; Jeong Ha Kim; Dae Young Hyun; Kyung Hoon Cho; Young Joon Hong; Ju Han Kim; Youngkeun Ahn; Manuel Hermida-Prieto; et al. (Tissue Engineering and Regenerative Medicine, 2024)

3D-printed NIR-responsive bullets as multifunctional nanodrug platforms for image-guided local chemo-photothermal therapy - Ginam Han; Hyun Lee; Jeon Min Kang; Jung-Hoon Park; Eunsol Lee; Eun Seong Lee; Sinwoo Park; Yuhyun Na; Min-Ho Kang; Nahyun Kim; Seo-Jun Bang; Kun Na; et al. (Chemical Engineering Journal, 2023)

Enhancing biodegradation of PBAT through bio-stimulation using Pseudozyma jejuensis for effective plastic waste reduction - Yewon Jang; Minseo Kim; Yeji Kim; Jaeyoung Yu; Sung-Kon Kim; Jeehoon Han; Yang-Hoon Kim; Jiho Min (Chemosphere, 2023)

Efficient MAPbI3-based perovskite solar cells exceeding 21% efficiency via aging treatment - Dae Woo Kim; Young Wook Noh; Jongmin Han; Hye Seung Kim; Chung Hyeon Jang; Ji A. Hong; Sangmi Park; Min Hyeong Lee; Ye In Kim; Myoung Hoon Song (Chemical Engineering Journal, 2023)

Stretchable and biodegradable triboelectric nanogenerator based on elastomeric nanocomposites - Heeseok Kang; Won Bae Han; Seung Min Yang; Gwan-Jin Ko; Yelynn Ryu; Joong Hoon Lee; Jeong-Woong Shin; Tae-Min Jang; Kaveti Rajaram; Sungkeun Han; Dong-Je Kim; Jun Hyeon Lim; et al. (Chemical Engineering Journal, 2023)

Green chemical and hybrid enzymatic pretreatments for lignocellulosic biorefineries: Mechanism and challenges - Rijuta Ganesh Saratale; Vinoth Kumar Ponnusamy; Grzegorz Piechota; Bartłomiej Igliński; S. Shobana; Jeong-Hoon Park; Ganesh Dattatraya Saratale; Han Seung Shin; J. Rajesh Banu; Vinod Kumar; Gopalakrishnan Kumar (Bioresource Technology, 2023)

Empirical estimation of size-resolved scavenging coefficients derived from in-situ measurements at background sites in Korea during 2013–2020 - Yongjoo Choi; Chang Hoon Jung; Junyoung Ahn; Seung-Myung Park; Kyung Man Han; Jongbyeok Jun; Giyeol Lee; Jiyoung Kim; Yongjae Lim; Kyeong-Sik Kang; Ilkwon Nam; Sumin Kim (Atmospheric Research, 2023)

Recent trends and perspectives of artificial intelligence-based machine learning from discovery to manufacturing in biopharmaceutical industry - Ravi Maharjan; Jae Chul Lee; Kyeong Lee; Hyo-Kyung Han; Ki Hyun Kim; Seong Hoon Jeong (Journal of Pharmaceutical Investigation, 2023)

Phytoplankton spring succession pattern in the Yellow Sea surveyed at Socheongcho Ocean Research Station - Myung Jin Hyun; Dong Han Choi; Howon Lee; Jongseok Won; Go-Un Kim; Yeonjung Lee; Jin-Young Jeong; Kongtae Ra; Wonseok Yang; Jaeik Lee; Jongmin Jeong; Charity Mijin Lee; et al. (Frontiers in Marine Science, 2023)
The spring phytoplankton bloom is a critical event in temperate oceans typically associated with the highest productivity levels throughout the year. To investigate the bloom process in the Yellow Sea, daily data on physical, chemical, and phytoplankton taxonomic group biomass, calculated via the chemotaxonomic approach, were collected from late March or early April to late May between 2018 and 2020 at the Socheongcho Ocean Research Station. During early spring (late March to mid-April), phytoplankton biomass increased, accompanied by a decrease in nutrient levels, with Bacillariophyceae and Cryptophyceae being the dominant groups. As water temperature increased, a pycnocline began to develop in late April, leading to a peak of the phytoplankton bloom dominated by chlorophytes and Cryptophyceae. Network analysis suggested that this phytoplankton bloom was caused by the onset of vertical stratification induced by increased sea surface temperature. The chlorophyte peak induced phosphate limitation above the pycnocline, resulting in succession to Prymnesiophyceae and Dinophyceae. Following pycnocline formation, phytoplankton biomass below the pycnocline was dominated by Bacillariophyceae and Cryptophyceae, with decreasing or fluctuating trends depending on phosphate concentration. Apart from these general patterns, 2019 and 2020 both had distinctive traits. The 2019 data revealed lower phosphate concentrations than the other 2 years, leading to a smaller chlorophyte peak at the surface compared to 2018 and extreme phosphate limitation above the pycnocline. This limitation resulted in decreased biomass of late successional groups, including Prymnesiophyceae and Dinophyceae. Pycnocline formation was delayed in year 2020, and stratification was significantly weaker compared to the previous 2 years. Due to the pycnocline delay, the surface chlorophyte peak did not develop and no succession to late successional groups was observed. Instead, high levels of Bacillariophyceae and Cryptophyceae biomass were observed throughout the water column with no surface bloom. Thus, among various environmental factors, increasing surface water temperature and phosphate concentrations play pivotal roles in shaping phytoplankton bloom dynamics. Distinct yearly variation points to the broader impacts of climate shifts, emphasizing the need for continued marine monitoring.

Repercussion of extracellular polymeric removal by low-temperature calcium peroxide pretreatment on bacterial fragmentation for enhancing biohydrogen production - Do-Hyung Kim; Han-Shin Kim; Baek-Gyu Im; Jeong-Hoon Park (Bioresource Technology, 2023)

Vulnerability assessment of Korean fisheries to climate change - Moo-Jin Kim; Jae-Beum Hong; In-Seong Han; Joon-Soo Lee; Do-Hoon Kim (Marine Policy, 2023)

Organic waste derived bioethanol supply chain network: Multiobjective snapshot model with a real-Korea case study - Oseok Kwon; Myungsuk Son; Juyeon Kim; Jee-hoon Han (Journal of Environmental Management, 2023)

Development of prediction model with machine learning in continuous twin screw granulation - Seung-Dong Yoo; Ji Yeon Kim; Sung-Kyun Han; Byung-Hoon Lee; Du Hyung Choi; Eun-Seok Park (Journal of Pharmaceutical Investigation, 2023)

Interaction diagrams of concrete-filled steel tube columns exposed to fire considering the slenderness effect - Han-Soo Kim; Jung-Hwan Lee; Seung-Hoon Lee (Engineering Structures, 2023)

Biodegradable, breathable, flexible, and electrically modulated all-leaf capacitive electronic skin for gesture recognition and human motion monitoring - Mohammad Zarei; Jung Hoon Kim; Joong Tark Han; Seung Goo Lee (Chemical Engineering Journal, 2023)

Cathode electrode architecture with facile ion percolating network assuring interfacial integrity for high-performance solid-state batteries - Kyung Oh Kim; Sang-Hoon Park; Ji Haeng Yu; Bo-Yun Jang; Chanhyun Park; Hye Woo Noh; Oi Lun Li; Sung-Kyun Jung; Yu-Jin Han (Chemical Engineering Journal, 2023)

SARS-CoV-2 3CL-protease inhibitors derived from ML300: investigation of P1 and replacements of the 1,2,3-benzotriazole - Alice Hooper; Jonathan D. Macdonald; Brenna Reilly; Joshua Maw; Aidan P. Wirrick; Sang Hoon Han; A. Abigail Lindsey; Emma G. Rico; Todd Romigh; Christopher M. Goins; Nancy S. Wang; Shaun R. Stauffer (Medicinal Chemistry Research, 2023)

Bloom development of toxic dinoflagellate Alexandrium catenella (Group I) in Jinhae-Masan Bay, Korea: Germination strategy of resting cysts in relation to temperature and salinity - Hyeon Ho Shin; Moon Ho Son; Bum Soo Park; Kyung Ha Han; Joo Yeon Youn; Kyeong Yoon Kwak; Ji Hoon Lee; A-Young Shin; Eunjung Byun; Yeong Du Yoo; Min Ho Seo; Kyungsoon Shin; et al. (Marine Pollution Bulletin, 2023)

Effects of the Probiotic Lactiplantibacillus plantarum KU15120 Derived from Korean Homemade Diced-Radish Kimchi Against Oxidation and Adipogenesis - Na-Kyoung Lee; Kyoung Jun Han; Hoon Park; Hyun-Dong Paik (Probiotics and Antimicrobial Proteins, 2023)

Seismic event and phase detection using deep learning for the 2016 Gyeongju earthquake sequence - Jongwon Han; Seongryong Kim; Dong-Hoon Sheen; Donghun Lee; Sang-Jun Lee; Seung-Hoon Yoo; Donghee Park (Geosciences Journal, 2023)

Systematic tracing of nitrate sources in a complex river catchment: An integrated approach using stable isotopes and hydrological models - Seung-Hee Kim; Dong-Hun Lee; Min-Seob Kim; Han-Pil Rhee; Jin Hur; Kyung-Hoon Shin (Water Research, 2023)

Inhibiting bacterial biofilm formation by stimulating c-di-GMP regulation using citrus peel extract from Jeju Island - Han-Shin Kim; So-Young Ham; Hwa-Soo Ryoo; Do-Hyung Kim; Eun-Tae Yun; Hee-Deung Park; Jeong-Hoon Park (Science of The Total Environment, 2023)

Preclinical Evaluation of an Everolimus-Eluting Bioresorbable Vascular Scaffold Via a Long-Term Rabbit Iliac Artery Model - Dae Sung Park; Myung Ho Jeong; Yu Jeong Jin; Mi Hyang Na; Doo Sun Sim; Munki Kim; Kyung Hoon Cho; Dae Young Hyun; Seok Oh; Jeong Ha Kim; Kyung Seob Lim; Jun-Kyu Park; et al. (Tissue Engineering and Regenerative Medicine, 2023)

Collinsella urealyticum sp. nov., a urease-positive bacterial strain isolated from swine faeces - Byeong Seob Oh; Seoung Woo Ryu; Seung Yeob Yu; Jeong Eun Bak; Won Jung Choi; Ji-Sun Kim; Jung-Sook Lee; Seung-Hwan Park; Se Won Kang; Jiyoung Lee; Mi-Kyung Lee; Won Yong Jung; et al. (Archives of Microbiology, 2023)

Fault activity on the inner continental shelf of the SE Korean Peninsula associated with back-arc opening and closing in the NW Pacific subduction zone - Seonghoon Moon; Han-Joon Kim; Chungho Kim; Su-hwan Lee; Sang Hoon Lee; Gi-Bom Kim (Marine Geophysical Research, 2023)

Extract of Styrax japonica attenuates glutamate-induced apoptosis via regulating MAPK signaling pathway in HT22 hippocampal cells - Da Hye Jeong; Song-I Han; Jae-Hoon Kim (Plant Biotechnology Reports, 2023)
Two-thirds of people with dementia suffer from Alzheimer’s disease, and there is a need to develop treatments with fewer side effects. Cholinergic and glutamate-induced brain damage occurs in the early stages of Alzheimer’s disease, so substances that suppress these symptoms may be potential candidates for the treatment. Ethanol extracts of 40 kinds of oriental medicine plants were examined whether they have acetylcholine esterase (Ache) inhibitory properties. We next investigated whether the ethanol extracts of six oriental medicine plants showing Ache inhibitory activity could inhibit glutamate-induced HT22 cell death. The ethanol extract of Styrax japonica (EESJ) was found to be relatively superior in both inhibitory activities. MTT and annexin V/PI staining assays confirmed that EESJ inhibited glutamate-induced apoptosis in the HT22 mouse hippocampal cells. EESJ also suppressed glutamate-mediated ROS production and attenuated the phosphorylation levels of MAPK members including ERK, JNK, and p38 kinases. Therefore, EESJ is a suitable candidate for developing a substance of Alzheimer’s disease treatment.

Elucidation of microbial interactions, dynamics, and keystone microbes in high pressure anaerobic digestion - Ajay Thapa; Jeong-Hoon Park; Seung Gu Shin; Hong-Mok Jo; Min-Sang Kim; Yeongmi Park; Uijeong Han; Si-Kyung Cho (Science of The Total Environment, 2023)

Genotoxicity assessment of root extracts of Paeonia lactiflora Pall - Su-Min Bak; Seng-Min Back; Da Yeon Kim; Na-Young Jeung; Nan-Young Kim; Jun-Young Yang; Kang-Hyun Han; Yong-Bum Kim; Byung Sun Min; Byoung-Seok Lee; Seong-Hoon Park (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Size-differential photosynthetic traits of phytoplankton in the Chukchi Sea - Sang H. Lee; Mi Sun Yun; Hyo Keun Jang; Jae Joong Kang; Kwanwoo Kim; Dabin Lee; Naeun Jo; Sang Hoon Park; Jang Han Lee; So Hyun Ahn; Dean A. Stockwell; Terry E. Whitledge (Continental Shelf Research, 2023)

Carbon shell-coated mackinawite FeS platelets as anode materials for high-performance sodium-ion batteries - Hyungsub Lim; Seunghyun Kim; Jung Hoon Kim; Hyo Chan Lee; Giwon Lee; Jong Hwan Park; Joong Tark Han; Kilwon Cho (Chemical Engineering Journal, 2023)

Highly efficient oxidation of single-walled carbon nanotubes in liquid crystalline phase and dispersion for applications in Li-ion batteries - Jung Hoon Kim; Junho Ahn; Han-Min Kim; Joon Young Cho; Do Geun Lee; Youngseok Oh; Jong Hwan Park; Jin Soo Kim; Jung-Keun Yoo; Joong Tark Han (Chemical Engineering Journal, 2023)

Facile low-energy and open-air synthesis of mixed-cation perovskite quantum dots for high-performance solar cells - Han Sol Yang; Dongwoon Lee; Eui Hyun Suh; Sung Hoon Noh; Kyeong Ho Lee; Jong Gyu Oh; Jaemin Jung; Jaeyoung Jang (Chemical Engineering Journal, 2023)

Facile low-energy and high-yield synthesis of stable α-CsPbI3 perovskite quantum dots: Decomposition mechanisms and solar cell applications - Han Sol Yang; Eui Hyun Suh; Sung Hoon Noh; Jaemin Jung; Jong Gyu Oh; Kyeong Ho Lee; Dongwoon Lee; Jaeyoung Jang (Chemical Engineering Journal, 2023)

Effects of temperature and starvation on life history traits and fatty acid profiles of the Antarctic copepod Tigriopus kingsejongensis - Deok-Seo Yoon; Hyuntae Choi; Alaa El-Din H. Sayed; Kyung-Hoon Shin; Joung Han Yim; Sanghee Kim; Min-Chul Lee; Jae-Seong Lee (Regional Studies in Marine Science, 2023)

Evaluating the comparative MT1B, MT1F, MT1G, and MT1H expression in human pulmonary alveolar epithelial cells treated with polyhexamethylene guanidine-phosphate, chloromethylisothiazolinone/methylisothiazolinone, oligo(2-(2-ethoxy)ethoxyethyl guanidinium chloride, benzalkonium chloride, and sodium dichloroisocyanurate - Jaeyoung Kim; Yong-Wook Baek; Cherry Kim; Yoon Jeong Nam; Yu-Seon Lee; Hong Lee; Ja Young Kang; Hyejin Lee; Jin Young Choi; Yoon Hee Park; Su A. Park; Eun-Kee Park; et al. (Molecular & Cellular Toxicology, 2023)

Gene expression related to lung cancer altered by PHMG-p treatment in PBTE cells - Yoon Hee Park; Sang Hoon Jeong; Hyejin Lee; Cherry Kim; Yoon Jeong Nam; Ja Young Kang; Jin Young Choi; Yu-Seon Lee; Su A. Park; Jaeyoung Kim; Eun-Kee Park; Yong-Wook Baek; et al. (Molecular & Cellular Toxicology, 2023)

A CHEMTAX Study Based on Picoeukaryotic Phytoplankton Pigments and Next-Generation Sequencing Data from the Ulleungdo–Dokdo Marine System of the East Sea (Japan Sea): Improvement of Long-Unresolved Underdetermined Bias - Myung Jin Hyun; Jongseok Won; Dong Han Choi; Howon Lee; Yeonjung Lee; Charity Mijin Lee; Chan Hong Park; Jae Hoon Noh (Journal of Marine Science and Engineering, 2022)
The CHEMTAX program has been widely used to estimate community composition based on major pigment concentrations in seawater. However, because CHEMTAX is an underdetermined optimization algorithm, underdetermined bias has remained an unsolved problem since its development in 1996. The risk of producing biased results increases when analyzing the picophytoplankton community; therefore, this study tested a new method for avoiding biased CHEMTAX results using the picophytoplankton community around the East Sea (Japan Sea). This method involves building a linear model between pigment concentration data and community composition data based on DNA sequencing to predict the pigment range for each operational taxonomic unit, based on the 95% prediction interval. Finally, the range data are transformed into an initial ratio and ratio limits for CHEMTAX analysis. Three combinations of initial ratios and ratio limits were tested to determine whether the modeled initial ratio and ratio limit could prevent underdetermined bias in the CHEMTAX estimates; these combinations were the modeled initial ratio and ratio limit, the modeled initial ratio with a default ratio limit of 500 s, and an initial ratio from previous research with the default ratio limit. The final ratio and composition data for each combination were compared with Bayesian compositional estimator-based final ratio and composition data, which are robust against underdetermined bias. Only CHEMTAX analysis using the modeled initial ratio and ratio limit was unbiased; all other combinations showed significant signs of bias. Therefore, the findings in this study indicate that ratio limits and the initial ratio are equally important in the CHEMTAX analysis of biased datasets. Moreover, we obtained statistically supported initial ratios and ratio limits through linear modeling of pigment concentrations and 16s rDNA composition data.

Antiviral activity of canine interferon lambda 3 expressed using a recombinant adenovirus against canine coronavirus, canine parvovirus, and canine distemper virus - Dong-Hwi Kim; Sang-Hoon Han; Hyeon-Jeong Go; Da-Yoon Kim; Jae-Hyeong Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Veterinary Research Communications, 2022)

Diversity study of common buckwheat germplasm in the Republic of Korea using GBS - Ji Eun Park; Yuna Kang; Gyung Deok Han; Mehtap Yildiz; Seong-Hoon Kim; Changsoo Kim; Yong Suk Chung (Plant Biotechnology Reports, 2022)

Estimation of the Benthic Habitat Zonation by Photo-Quadrat Image Analysis along the Fringing Reef of Weno Island, Chuuk, Micronesia - Taihun Kim; Dae-Won Lee; Han-Jun Kim; Yun-Hwan Jung; Young-Ung Choi; Jung-Hee Oh; Tae-Hoon Kim; Do-Hyung Kang; Heung-Sik Park (Journal of Marine Science and Engineering, 2022)
Benthic habitat zonation is described from in situ observations and seabed photographs taken from the coastal area of Weno Island, Chuuk, Micronesia. Habitat groups, types, and boundaries are defined by visible substratum characteristics (i.e., in situ and by digital imaging of photo-quadrats along transect lines), and by cluster and ordination analyses using relative coverage percentage of identified classification categories. The statistical similarity between habitat groups is determined by Analysis of similarity (ANOSIM). Benthic habitat groups with significant influence on the determination of habitat type are isolated by the similarity percentage (SIMPER) test. In addition to the standard practices of using transect lines and collecting data in accordance with the already well-implemented and thoroughly-tested benthic habitat classification scheme for tropical reef monitoring, we applied simple statistics that enable comparative data interpretation. Our simple, repeatable methods provide a framework for benthic habitat-related monitoring research that allows the comparison of results across regions.

Factors governing seawater carbonate dynamics in a macroalgal habitat - Ja-Myung Kim; Kitack Lee; In-Seong Han; Miok Kim; Ju-Hyoung Kim; Tae-Hoon Kim; HyunKyum Kim; Byung Hee Jeon; Kyoungsoon Shin (Frontiers in Marine Science, 2022)
Photosynthetic organisms shift the dynamics of surface pCO 2 driven by the sea surface temperature change (thermodynamic driver) by assimilating inorganic C from seawater. Here we measured net C uptake in a macroalgal habitat of coastal Korea for two years (2019-2020) and found that the macroalgal habitat contributed 5.8 g C m −2 month −1 of the net C uptake during the growing period (the cooling period, September−May). This massive C uptake changed the thermodynamics-driven seasonal dynamics such that the air−sea equilibrium of pCO 2 was pushed into disequilibrium. The surface pCO 2 dynamics during the cooling period was mostly influenced by the seasonal decrease in temperature and the proliferation of macroalgae, while the dynamics during the warming period (the stagnant period, June−August) closely followed that predicted based solely on the change in sea surface temperature (thermodynamic driver). In contrast to the phytoplankton-dominated off-shore waters (where phytoplankton populations are large in spring and summer), the impact of coastal macroalgae on surface pCO 2 dynamics was most pronounced during the cooling period, when the magnitude of pCO 2 change was as much as twice that resulting from temperature change. Our study shows that the distinctive features of the macroalgal habitat—in particular the seasonal temperature extremes (~18°C difference), the active macroalgal metabolism, and anthropogenic nutrient inputs—collectively influenced the seasonal decoupling of seawater and air pCO 2 dynamics.

Neotectonics at the SE Continental Margin of the Korean Peninsula: Implications for the Back-Arc Region Behind the SW Japan Arc - Han-Joon Kim; Seonghoon Moon; Chungho Kim; Kwang-Hee Kim; Wooseok Seo; Kwang-Hyun Cho; Hye-Jin Moon; Gwang Hoon Lee (Pure and Applied Geophysics, 2022)

Potential Short-Term Effects of Mine Tailings on Phytoplankton Assemblages in the Open Ocean - Dong Han Choi; Jangyeon Yoo; Wonseok Yang; Jae Hoon Noh; Yeonjung Lee; Kongtae Ra; Kiseong Hyeong; Chan Min Yoo; Jisoo Park (Journal of Marine Science and Engineering, 2022)
The disposal of mine tailings into the marine environment is considered an essential option to secure the economic efficiency of deep-sea mining, but it might adversely affects the ecosystem. To examine the potential impacts of tailing disposal from polymetallic nodules and polymetallic sulfide mines on phytoplankton communities, addition experiments of crushed fine particles into surface seawater were conducted in the open Indian Ocean and changes in chlorophyll a fluorescence and community composition were analyzed. The addition of tailings had serious adverse effects on phytoplankton fluorescence and photosynthetic activity, regardless of mine type. The adverse effects seemed to mainly be due to the physical properties of the mine tailings. These also showed discriminatory effects on phytoplankton, resulting in great changes in community composition. The results suggest that mine tailings could have significant adverse impacts on phytoplankton assemblages, but the degree of impact greatly varies depending on the phytoplankton groups. The discriminatory impacts would cause changes in biomass, community structure, and thus ecological function.

Enhanced Bone Regeneration by Bone Morphogenetic Protein-2 after Pretreatment with Low-Intensity Pulsed Ultrasound in Distraction Osteogenesis - Jeong Joon Han; Hoon Joo Yang; Soon Jung Hwang (Tissue Engineering and Regenerative Medicine, 2022)

Asymmetric Contribution of Blastomere Lineages of First Division of the Zygote to Entire Human Body Using Post-Zygotic Variants - Seong Gyu Kwon; Geon Hue Bae; June Hyug Choi; Nanda Maya Mali; Mee Sook Jun; Dong Sun Kim; Man-Hoon Han; Seongyeol Park; Young Seok Ju; Seock Hwan Choi; Ji Won Oh (Tissue Engineering and Regenerative Medicine, 2022)

Anti-adipogenic Effects of the Probiotic Lactiplantibacillus plantarum KU15117 on 3T3-L1 Adipocytes - Kyoung Jun Han; Na-Kyoung Lee; Hyung-Seok Yu; Hoon Park; Hyun-Dong Paik (Probiotics and Antimicrobial Proteins, 2022)

Correlation of seismicity with geologic structures at the middle eastern Korean margin in the East Sea (Japan Sea) and seismic hazard assessment - Seonghoon Moon; Han-Joon Kim; Kwang-Hee Kim; Dong-Geun Yoo; Sang-Hoon Lee; Woo-Hyun Son; Bo Yeon Yi (Marine Geophysical Research, 2022)

Prognostic significance of three endothelial nitric oxide synthase (eNOS) polymorphisms and metabolic syndrome (MetS) in patients with colorectal cancer - Eun Ju Ko; Eo Jin Kim; Hye Jung Cho; Jisu Oh; Han Sung Park; Chang Soo Ryu; Jung Oh Kim; Hak Hoon Jun; So Young Chong; Jong Woo Kim; Nam Keun Kim (Genes & Genomics, 2022)

Inner surface modification of ureteral stent polyurethane tubes based by plasma-enhanced chemical vapor deposition to reduce encrustation and biofilm formation - Hyuna Lim; Jae Hoon Chung; Yoonsoo Park; Namwuk Baek; Youngsik Seo; Heonyong Park; Yong Ki Cho; Donggeun Jung; Deok Hyun Han (Biofouling, 2022)

Potential of a Tintinnid Species, Tintinnidium primitivum, as a Biological Indicator in the Yellow Sea Bottom Cold Water - Young Ok Kim; Jungmin Choi; Kyung-Hee Oh; Dong Han Choi; Jae Hoon Noh; Wonseok Yang; Myung Jin Hyun (Ocean Science Journal, 2022)

Distribution of dissolved organic carbon linked to bacterial community composition during the summer melting season in Arctic fjords - Dukki Han; Moonho Son; Ki-Hyuk Eom; Young-Tae Park; MinKyu Choi; Jeonghyun Kim; Tae-Hoon Kim (Polar Biology, 2022)

Marinobacter arenosus sp. nov., a halotolerant bacterium isolated from a tidal flat - Yunjeong Lee; Veeraya Weerawongwiwat; Jong-Hwa Kim; Min Kuk Suh; Han Sol Kim; Jung-Sook Lee; Jung-Hoon Yoon; Ampaitip Sukhoom; Wonyong Kim (Archives of Microbiology, 2022)

Arenibacterium arenosum sp. nov., isolated from sea sand - Jiseon Jeong; Veeraya Weerawongwiwat; Jong-Hwa Kim; Min Kuk Suh; Han Sol Kim; Jung-Sook Lee; Jung-Hoon Yoon; Ampaitip Sukhoom; Wonyong Kim (Archives of Microbiology, 2022)

Short-term effects of exposure to particulate matter and air pollution on hospital admissions for asthma and chronic obstructive pulmonary disease in Gyeonggi-do, South Korea, 2007–2018 - Chang Hoon Han; Haeyong Pak; Jae Ho Chung (Journal of Environmental Health Science and Engineering, 2021)

Tiller Outgrowth in Rice (Oryza sativa L.) is Controlled by OsGT1, Which Acts Downstream of FC1 in a PhyB-Independent Manner - Vikranth Kumar; Sung Hoon Kim; Moch Rosyadi Adnan; Jung Heo; Jin Hee Jeong; Ryza A. Priatama; Jeung Joo Lee; Chul Min Kim; Byoung Il Je; Soon Ju Park; Yuan Hu Xuan; Chang-deok Han (Journal of Plant Biology, 2021)

Liposoluble portion of the red alga Pyropia yezoensis protects alcohol induced liver injury in mice - Ji-Hyeok Lee; Ginne Ahn; Ju-Young Ko; Nalae Kang; Kyungsook Jung; Eui-Jeong Han; Gwang-Hoon Kim; Hee Jeong Kim; Cheol Soo Choi; You-Jin Jeon (Algae, 2021)
The hepatoprotective effect of liposoluble portion of Pyropia yezoensis (PYLP) was investigated against alcohol-induced liver injury in mice. Fatty acids were predominant in PYLP obtained from hexane fraction of 70% EtOH extract after ultrasonication. In particular, polyunsaturated fatty acids such as eicosapentaenoic acid and linoleic acid accounted for 56.91% of the total lipids. PYLP significantly reduced liver damage induced by the alcohol treatment in mice. PYLP treatment increased the activity of antioxidant enzymes including superoxide dismutase, catalase, and glutathion peroxidase by reducing thiobarbituric acid reactive substances. Histological observations showed that PYLP minimizes damage to living tissue induced by alcohol treatment by modulating the expression level of proteins involved in the anti-apoptotic signaling pathway. Our results suggest that PYLP, rich in polyunsaturated fatty acids extracted from the red alga P. yezoensis, will be useful as a potential liver protectant in the hangover industry.

Effects of rifampicin on hepatic antioxidant enzymes in PXR and CAR double humanized mice - Young Jae Choi; Chang Seon Ryu; Sang Yoon Lee; Ha Gyeong Kim; Nan Young Kim; Ji-Yoon Lee; Soo Jin Oh; Han-Jin Park; Seung-Woo Cho; Jong-Hoon Kim; Sang Kyum Kim (Molecular & Cellular Toxicology, 2021)

IL-10 Deficiency Aggravates Renal Inflammation, Fibrosis and Functional Failure in High-Fat Dieted Obese Mice - Dae Hwan Kim; So Young Chun; EunHye Lee; Bomi Kim; BoHyun Yoon; Haejung Gil; Man-Hoon Han; Yun-Sok Ha; Jun Nyung Lee; Tae Gyun Kwon; Bum Soo Kim; Byung Ik Jang (Tissue Engineering and Regenerative Medicine, 2021)
BACKGROUND: High-fat diet-induced obesity is one of the major cause of chronic renal failure. This obesity-related renal failure is mainly caused by inflammatory processes. However, the role of the major anti-inflammatory cytokine interleukin (IL)-10 has not been researched intensively. METHODS: To evaluate the effect of IL-10 deficiency on obesity-related renal failure, the in vivo study was carried with four animal groups; (1) Low-fat dieted C57BL/6 mice, (2) Low-fat dieted IL-10 knockout (KO) mice, (3) High‐fat dieted C57BL/6 mice and (4) High‐fat dieted IL-10 KO mice group. The analysis was carried with blood/urine chemistry, H&E, Oil-Red-O, periodic acid-Schiff and Masson’s trichrome staining immunohistochemistry and real-time PCR methods. RESULTS: At week 12, high‐fat dieted IL-10 KO mice showed 1) severe lipid accumulation in kidneys, cholesterol elevation (in total, serum kidney) and low-density lipoprotein increasion through the SCAP-SREBP2-LDLr pathway; (2) serious histopathologic alterations showing glomerulosclerosis, tubulointerstitial fibrosis and immune cell infiltration; (3) increased pro‐inflammatory cytokines and chemokines expression; (4) enhanced renal fibrosis; and (5) serious functional failure with high serum creatinine and BUN and proteinuria excretion compared to other groups. CONCLUSION: IL-10 deficiency aggravates renal inflammation, fibrosis and functional failure in high-fat dieted obese mice, thus IL-10 therapy could be applied to obesity-related chronic renal failure.

Aquaculture Farming Effect on Benthic Respiration and Nutrient Flux in Semi-Enclosed Coastal Waters of Korea - Sung-Han Kim; Jae-Seong Lee; Kyung-Tae Kim; Hyung-Chul Kim; Won-Chan Lee; Dongmun Choi; Sang-Hwa Choi; Jae-Hoon Choi; Hyo-Jin Lee; Jae-Hyuk Shin (Journal of Marine Science and Engineering, 2021)
Sediment oxygen demand (SOD) and benthic nutrient fluxes (BNFs) were measured using an in situ benthic chamber at a fish farm (FF), oyster farm (OF), and controls (FF-C and OF-C) to assess the impact of aquaculture activities on organic carbon (OC) and nutrients cycles in coastal waters of Korea. The SOD at FF and OF ranged from 60 ± 2 to 157 ± 3 mmol m−2 d−1 and from 77 ± 14 to 84 ± 16 mmol m−2 d−1, respectively, more than five times those of the control sites. The SOD at farm sites is highly correlated with fish stock and food input, suggesting that excess feed input is an important control factor for OC remineralization. The combined analysis of sediment trap and SOD indicates that most of the deposited OC oxidized in the sediment and/or was laterally transported by the current before being buried in the sediment. The benthic nutrient fluxes at farms ranged from 5.45 to 8.95 mmol N m−2 d−1 for nitrogen and from 0.51 to 1.67 mmol P m−2 d−1 for phosphate, respectively, accounting for 37–270% and 52–804% of the N and P required for primary production in the water column. These results indicate that aquaculture farming may profoundly impact biogeochemical cycles in coastal waters.

Latest Quaternary mass-transport processes of fan-shaped body in the western margin of the Ulleung Basin, East Sea (Japan Sea) - Sang-Hoon Lee; Hyeong-Tae Jou; Jang-Jun Bahk; Hyunggu Jun; Seong-Hoon Moon; Han-Joon Kim; Senay Horozal; Deniz Cukur; In-Kwon Um; Dong-Geun Yoo; Roger Urgeles (Geosciences Journal, 2021)

Association of genetic variants of RNF213 with ischemic stroke risk in Koreans - Young Seok Park; Hyeon Woo Park; Han Sung Park; Chang Soo Ryu; Jeong Yong Lee; Eun Ju Ko; Jung Hoon Sung; Jinkwon Kim; Ok Joon Kim; Nam Keun Kim (Genes & Genomics, 2021)

Spring Distribution of Ciliate Plankton in the Southeastern Yellow Sea in 2019 - Young Ok Kim; Jungmin Choi; Hyung-Ku Kang; Jae Hoon Noh; Dong Han Choi; Kyung-Hee Oh (Ocean Science Journal, 2021)

Comparative transcriptome profiling of two sweetpotato cultivars with contrasting flooding stress tolerance levels - Sul-U Park; Yun-Hee Kim; Chan-Ju Lee; So-Eun Kim; Ye-Hoon Lim; Ung-Han Yoon; Ho Soo Kim; Sang-Soo Kwak (Plant Biotechnology Reports, 2020)

Random noise attenuation of sparker seismic oceanography data with machine learning - Hyunggu Jun; Hyeong-Tae Jou; Chung-Ho Kim; Sang Hoon Lee; Han-Joon Kim (Ocean Science, 2020)
Seismic oceanography (SO) acquires water column reflections using controlled source seismology and provides high lateral resolution that enables the tracking of the thermohaline structure of the oceans. Most SO studies obtain data using air guns, which can produce acoustic energy below 100 Hz bandwidth, with vertical resolution of approximately 10 m or more. For higher-frequency bands, with vertical resolution ranging from several centimeters to several meters, a smaller, low-cost seismic exploration system may be used, such as a sparker source with central frequencies of 250 Hz or higher. However, the sparker source has a relatively low energy compared to air guns and consequently produces data with a lower signal-to-noise (S∕N) ratio. To attenuate the random noise and extract reliable signal from the low S∕N ratio of sparker SO data without distorting the true shape and amplitude of water column reflections, we applied machine learning. Specifically, we used a denoising convolutional neural network (DnCNN) that efficiently suppresses random noise in a natural image. One of the most important factors of machine learning is the generation of an appropriate training dataset. We generated two different training datasets using synthetic and field data. Models trained with the different training datasets were applied to the test data, and the denoised results were quantitatively compared. To demonstrate the technique, the trained models were applied to an SO sparker seismic dataset acquired in the Ulleung Basin, East Sea (Sea of Japan), and the denoised seismic sections were evaluated. The results show that machine learning can successfully attenuate the random noise in sparker water column seismic reflection data.

NH4+ Suppresses NO3–-Dependent Lateral Root Growth and Alters Gene Expression and Gravity Response in OsAMT1 RNAi Mutants of Rice (Oryza sativa) - Vikranth Kumar; Sung Hoon Kim; Ryza A. Priatama; Jin Hee Jeong; Moch Rosyadi Adnan; Bernet Agung Saputra; Chul Min Kim; Byoung Il Je; Soon Ju Park; Ki Hong Jung; Kyung Min Kim; Yuan Hu Xuan; et al. (Journal of Plant Biology, 2020)

Characterization of genetic variation and antioxidant properties in strawberry (Fragaria × ananassa Duch.) mutant genotypes - Jaihyunk Ryu; Woon Ji Kim; Sang Hun Kim; Kang-Seop Lee; Han-Jig Jo; Ee-Youb Kim; Sang Hoon Kim; Si-Yong Kang; Jeong-Hee Lee; Bo-Keun Ha (Genetic Resources and Crop Evolution, 2020)

Genome-wide analysis of brassinosteroid responsive small RNAs in Arabidopsis thaliana - So Young Park; Jae-Han Choi; Dong-Ha Oh; John C. Johnson; Maheshi Dassanayake; Dong-Hoon Jeong; Man-Ho Oh (Genes & Genomics, 2020)

Wax-printed well pads and colorimetric LAMP detection of ApxIA toxin gene - SeonHyung Lee; Ji Hun Kim; Beom-Ku Han; Won-Il Kim; Byung-Kwan Cho; Sung Min Woo; Yang-Hoon Kim; Ji-Young Ahn (Molecular & Cellular Toxicology, 2020)

Association between human gray matter metabotropic glutamate receptor-5 availability in vivo and white matter properties: a [11C]ABP688 PET and diffusion tensor imaging study - Song E. Kim; Yo-Han Joo; Young-Don Son; Hang-Keun Kim; Sang-Yoon Lee; Min-Woo Lee; Tatsuo Ido; Jong-Hoon Kim (Brain Structure and Function, 2020)

The gene repertoire of Pythium porphyrae (Oomycota) suggests an adapted plant pathogen tackling red algae - Yacine Badis; Jong Won Han; Tatyana A. Klochkova; Claire M. M. Gachon; Gwang Hoon Kim (Algae, 2020)

Diverse Gene Expressions in the Prediction of Cuprizone-Induced Demyelination - Seung Ro Han; Yun Hee Kang; Seung-Min Yoo; Myung-Shin Lee; Seung-Hoon Lee (Neurotoxicity Research, 2020)

Combination of Human Mesenchymal Stem Cells and Repetitive Transcranial Magnetic Stimulation Enhances Neurological Recovery of 6-Hydroxydopamine Model of Parkinsonian’s Disease - Ji Yong Lee; Hyun Soo Kim; Sung Hoon Kim; Han-Soo Kim; Byung Pil Cho (Tissue Engineering and Regenerative Medicine, 2020)

Genetic and phylogenetic structure of Hynobius quelpaertensis, an endangered endemic salamander species on the Korean Peninsula - Ho Young Suk; Han-Gyu Bae; Dong-Young Kim; Hari Won; Hae Jun Baek; Chang Hoon Lee; Dong Youn Kim; Young Min Go; Jae-Young Song; Hang Lee; Mi-Sook Min (Genes & Genomics, 2020)

Stem Cell Mechanosensation on Gelatin Methacryloyl (GelMA) Stiffness Gradient Hydrogels - Claire Kim; Jennifer L. Young; Andrew W. Holle; Kwanghee Jeong; Luke G. Major; Ji Hoon Jeong; Zachary M. Aman; Dong-Wook Han; Yongsung Hwang; Joachim P. Spatz; Yu Suk Choi (Annals of Biomedical Engineering, 2020)

Transposable element-mediated structural variation analysis in dog breeds using whole-genome sequencing - Songmi Kim; Seyoung Mun; Taemook Kim; Kang-Hoon Lee; Keunsoo Kang; Je-Yoel Cho; Kyudong Han (Mammalian Genome, 2019)

Association of COX2 −765G>C promoter polymorphism and coronary artery disease in Korean population - In Jai Kim; Sang Hoon Kim; Dong Hoon Cha; Sang Wook Lim; Jae Youn Moon; Jung Oh Kim; Chang Soo Ryu; Han Sung Park; Jung Hoon Sung; Nam Keun Kim (Genes & Genomics, 2019)

Preparation and Characterization of Human Adipose Tissue-Derived Extracellular Matrix, Growth Factors, and Stem Cells: A Concise Review - So Young Chun; Jeong Ok Lim; Eun Hye Lee; Man-Hoon Han; Yun-Sok Ha; Jun Nyung Lee; Bum Soo Kim; Min Jeong Park; MyungGu Yeo; Bongsu Jung; Tae Gyun Kwon (Tissue Engineering and Regenerative Medicine, 2019)

Methoxetamine Induces Cytotoxicity in H9c2 Cells: Possible Role of p21 Protein (Cdc42/Rac)-Activated Kinase 1 - Kyung Sik Yoon; Sun Mi Gu; Santosh Lamichhane; Kyoung Moon Han; Jisoon Shin; Young-Hoon Kim; Soo Kyung Suh; Hye Jin Cha; Jaesuk Yun (Cardiovascular Toxicology, 2019)

Transgenic Arabidopsis plants expressing CsBCATs affect seed germination under abiotic stress conditions - Jeong Hwan Lee; Ji Hoon Han; Young-Cheon Kim; Young Hee Lee; Jeum Kyu Hong; Sanghyeob Lee (Plant Biotechnology Reports, 2019)

A Chloroplast-targeted S1 RNA-binding Domain Protein Plays a Role in Arabidopsis Response to Diverse Abiotic Stresses - Sy Nguyen Dinh; Su Jung Park; Ji Hoon Han; Hunseung Kang (Journal of Plant Biology, 2019)

The overexpression of cucumber (Cucumis sativus L.) genes that encode the branched-chain amino acid transferase modulate flowering time in Arabidopsis thaliana - Jeong Hwan Lee; Young-Cheon Kim; Youjin Jung; Ji Hoon Han; Chunying Zhang; Cheol-Won Yun; Sanghyeob Lee (Plant Cell Reports, 2019)

Hymenobacter agri sp. nov., a novel bacterium isolated from soil - Jigon Han; Leonid N. Ten; Dong Hoon Lee; In-Kyu Kang; Hee-Young Jung (Antonie van Leeuwenhoek, 2018)

Neotectonics of the Eastern Korean Margin Inferred from Back-arc Rifting Structure - Han-Joon Kim; Hyeong-Tae Jou; Gwang Hoon Lee (Ocean Science Journal, 2018)

Improvement of cellular uptake of hydrophilic molecule, calcein, formulated by liposome - Su-Min Han; Young-Guk Na; Han-Sol Lee; Gi-Ho Son; Seong-Hoon Jeon; Ki-Hyun Bang; Sung-Jin Kim; Hye-Jin Lee; Cheong-Weon Cho (Journal of Pharmaceutical Investigation, 2018)

In Vivo Validation Model of a Novel Anti-Inflammatory Scaffold in Interleukin-10 Knockout Mouse - Jung Yeon Kim; So Young Chun; Sang Hoon Lee; Eugene Lih; Jeongshik Kim; Dae Hwan Kim; Yun-Sok Ha; Jae-Wook Chung; Jun Nyung Lee; Bum Soo Kim; Hyun Tae Kim; Eun Sang Yoo; et al. (Tissue Engineering and Regenerative Medicine, 2018)

Evidence of hepatitis E virus infection in specific pathogen-free rabbits in Korea - Sang-Hoon Han; Byung-Joo Park; Hee-Seop Ahn; Yong-Hyun Kim; Hyeon-Jeong Go; Dong-Hwi Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Virus Genes, 2018)

Next-generation sequencing reveals the diversity of benthic diatoms in tidal flats - Sung Min An; Dong Han Choi; Howon Lee; Jung Ho Lee; Jae Hoon Noh (Algae, 2018)

Optimization of TILLING system based on capillary electrophoresis for targeted selection of pepper gene mutants - Han Sol Kang; Sang Hoon Kim; Sang Woo Lee; Se Won Kim; Jaihyunk Ryu; Jin-Baek Kim; Seon-In Yeom; Si-Yong Kang; Yeong Deuk Jo (Horticulture, Environment, and Biotechnology, 2018)

Differences between immunodeficient mice generated by classical gene targeting and CRISPR/Cas9-mediated gene knockout - Jae Hoon Lee; Jong-Hyung Park; Tae-Wook Nam; Sun-Min Seo; Jun-Young Kim; Han-Kyul Lee; Jong Hyun Han; Song Yi Park; Yang-Kyu Choi; Han-Woong Lee (Transgenic Research, 2018)

BPH1, a novel substrate receptor of CRL3, plays a repressive role in ABA signal transduction - Og-Geum Woo; Soon-Hee Kim; Seok Keun Cho; Sang-Hoon Kim; Han Nim Lee; Taijoon Chung; Seong Wook Yang; Jae-Hoon Lee (Plant Molecular Biology, 2018)

Proteomic analysis of muscarinic acetylcholine receptor-mediated proliferation in HT-29 human colon cancer cells - Soo Youn Lee; Ar-Reum Lee; Ji-Young Ahn; Jung Ho Ko; Lyon Lee; Janet Han; Young-Chang Kim; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2018)

Phylogeography of the Asian lesser white-toothed shrew, Crocidura shantungensis, in East Asia: role of the Korean Peninsula as refugium for small mammals - Seo-Jin Lee; Mu-Yeong Lee; Liang-Kong Lin; Y. Kirk Lin; Yuchun Li; E-Hyun Shin; Sang-Hoon Han; Mi-Sook Min; Hang Lee; Kyung Seok Kim (Genetica, 2018)

RNA expression, protein activity, and interactions in the ACC synthase gene family in cucumber (Cucumis sativus L.) - Jeong Hwan Lee; Young-Cheon Kim; Daeun Choi; Ji Hoon Han; Youjin Jung; Sanghyeob Lee (Horticulture, Environment, and Biotechnology, 2018)

Effects of 1-methylcyclopropene (1-MCP) and polyethylene (PE) film liner treatments on the fruit quality of cold-stored ‘Gamhong’ apples - Kyoung-ook Kim; Jingi Yoo; Jinwook Lee; Nay Myo Win; Seulgi Ryu; Jeung-Sul Han; Hee-Young Jung; Myoung-Gun Choung; Yong-Deuk Kwon; Dong Hoon Lee; In-Kyu Kang (Horticulture, Environment, and Biotechnology, 2018)

Correction to: Determining soil quality in urban agricultural regions by soil enzyme-based index - Avanthi Deshani Igalavithana; Muhammad Farooq; Kye-Hoon Kim; Young-Han Lee; Muhammad Farooq Qayyum; Mohammad I. Al-Wabel; Sang Soo Lee; Yong Sik Ok (Environmental Geochemistry and Health, 2018)

Current Understanding of Stem Cell and Secretome Therapies in Liver Diseases - Dongkyu Kim; Gun-Sik Cho; Choongseong Han; Dong-Hyuk Park; Hee-Kyung Park; Dong-Hun Woo; Jong-Hoon Kim (Tissue Engineering and Regenerative Medicine, 2017)

Effects of temperature and salinity on the asexual reproduction of Nemopilema nomurai (Scyphozoa: Rhizostomeae) - Hye Eun Lee; Chang Hoon Han; ByeongHo Kim; Won Duk Yoon (Ocean Science Journal, 2017)

A synthetic cannabinoid JWH-210 reduces lymphoid organ weights and T-cell activator levels in mice via CB2 receptors - Sun Mi Gu; Hyun Jin Lee; Tac-hyung Lee; Yun Jeong Song; Young-Hoon Kim; Kyoung-Moon Han; Jisoon Shin; Hye-Kyung Park; Hyung Soo Kim; Hye Jin Cha; Jaesuk Yun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Heterogeneous expression of Chlamydia pneumoniae antigen candidates and high-level soluble expression of its inclusion membrane proteins in Escherichia coli - Soo Youn Lee; Sunjin Lee; Ji-Young Ahn; Jung Ho Ko; Lyon Lee; Janet Han; Young-Chang Kim; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2017)

Determining soil quality in urban agricultural regions by soil enzyme-based index - Avanthi Deshani Igalavithana; Muhammad Farooq; Kye-Hoon Kim; Young-Han Lee; Muhammad Farooq Qayyum; Mohammad I. Al-Wabel; Sang Soo Lee; Yong Sik Ok (Environmental Geochemistry and Health, 2017)

A nationwide study of the incidence rate of herb-induced liver injury in Korea - Jung-Hyo Cho; Dal-Seok Oh; Sang-Hoon Hong; Heung Ko; Nam-Hun Lee; Sang-Eun Park; Chang-Woo Han; Seung-Mo Kim; Young-Chul Kim; Kang-San Kim; Chang-Won Choi; Seon-My Shin; et al. (Archives of Toxicology, 2017)

Decline patterns and risk assessment of 10 multi-class pesticides in young sprout amaranth (Amaranthus mangostanus) under greenhouse growing conditions - In Kyung Kim; Sung-Woo Kim; A. M. Abd El-Aty; Md. Musfiqur Rahman; Md. Humayun Kabir; Han Sol Lee; Hyung Suk Chung; Ji Hoon Jeong; Ho-Chul Shin; Jae-Han Shim (Environmental Science and Pollution Research, 2017)

The stabilization of biopharmaceuticals: current understanding and future perspectives - Jae Geun Song; Sang Hoon Lee; Hyo-Kyung Han (Journal of Pharmaceutical Investigation, 2017)

Dissipation kinetics, pre-harvest residue limits, and hazard quotient assessments of pesticides flubendiamide and fluopicolide in Korean melon (Cucumis melo L. var. makuwa) grown under regulated conditions in plastic greenhouses - Md. Humayun Kabir; A. M. Abd El-Aty; Md. Musfiqur Rahman; Sung-Woo Kim; Han Sol Lee; Hyung Suk Chung; Jung Ah Do; Ji Hoon Jeong; Byung-Joon Chang; Moon Ik Chang; Ho-Chul Shin; Jae-Han Shim (Environmental Science and Pollution Research, 2017)

Imaging the Yellow Sea Bottom Cold Water from multichannel seismic data - Hye-Jin Moon; Han-Joon Kim; Chung-Ho Kim; Seonghoon Moon; Su-hwan Lee; Jin Soo Kim; Chung-Kyun Jeon; Gwang Hoon Lee; Sang Hoon Lee; YoungSook Baek; Hyeong-Tae Jou (Journal of Oceanography, 2017)

Mapping the Patent Landscape in the Field of Personalized Medicine - Chie Hoon Song; Jeung-Whan Han; Byeongki Jeong; Janghyeok Yoon (Journal of Pharmaceutical Innovation, 2017)

Effects of temperature on growth and fatty acid synthesis in the cyclopoid copepod Paracyclopina nana - Seung-Hwi Lee; Min-Chul Lee; Jayesh Puthumana; Jun Chul Park; Sujin Kang; Jeonghoon Han; Kyung-Hoon Shin; Heum Gi Park; Ae-Son Om; Jae-Seong Lee (Fisheries Science, 2017)

Proteomic profiles of Daphnia magna exposed to lead (II) acetate trihydrate and atrazine - Vu Quynh Anh Le; Ji-Young Ahn; Mi Young Heo; Sung-Jin Cho; Hobaek Yoon; Jihoo Park; Jung Ho Ko; Lyon Lee; Janet Han; Sang Yong Kim; Yang-Hoon Kim; Jiho Min (Genes & Genomics, 2017)

Effects of biocontrol with an atyid shrimp (Caridina denticulata) and a bagrid catfish (Pseudobagrus fulvidraco) on toxic cyanobacteria bloom (Microcystis aeruginosa) in a eutrophic agricultural reservoir - Min-Seob Kim; Yeonjung Lee; Seongjin Hong; Soon-Jin Hwang; Baik-Ho Kim; Kwang-Guk An; Young-Seuk Park; Sang-Kyu Park; Han-Yong Um; Kyung-Hoon Shin (Paddy and Water Environment, 2017)

A simple method of correction for profile-length water-column height variations in high-resolution, shallow-water seismic data - Hyeonju Kim; Gwang Hoon Lee; Bo Yeon Yi; Youngho Yoon; Kyong-O Kim; Han-Joon Kim; Sang Hoon Lee (Ocean Science Journal, 2017)

Inhalation Toxicity of Bisphenol A and Its Effect on Estrous Cycle, Spatial Learning, and Memory in Rats upon Whole-Body Exposure - Yong Hyun Chung; Jeong Hee Han; Sung-Bae Lee; Yong-Hoon Lee (Toxicological Research, 2017)

Simulations of the Population Dynamics of Jellyfish Polyps Living on Artificial Substrates in Coastal Areas - Hong Sung Jin; Dongyeob Han; Jung-Hun Kim; Hyun-Jae Shin; Yang Ho Yoon; Chang-hoon Han (Thalassas: An International Journal of Marine Sciences, 2017)

Identification and functional analysis of a promoter sequence for phloem tissue specific gene expression from Populus trichocarpa - Van Phap Nguyen; Jin-Seong Cho; Ji-Hoon Lee; Min-Ha Kim; Young-Im Choi; Eung-Jun Park; Won-Chan Kim; Seongbin Hwang; Kyung-Hwan Han; Jae-Heung Ko (Journal of Plant Biology, 2017)

Behavioral responses of chinstrap and gentoo penguins to a stuffed skua and human nest intruders - Won Young Lee; Jin-Woo Jung; Han-Gu Choi; Hosung Chung; Yeong-Deok Han; Sam-Rae Cho; Jeong-Hoon Kim (Polar Biology, 2017)

Breeding records of kelp gulls in areas newly exposed by glacier retreat on King George Island, Antarctica - Won Young Lee; Hyun-Cheol Kim; Yeong-Deok Han; Chang-Uk Hyun; Seongseop Park; Jin-Woo Jung; Jeong-Hoon Kim (Journal of Ethology, 2017)

Construction of mutation populations by gamma-ray and carbon beam irradiation in chili pepper (Capsicum annuum L.) - Yeong Deuk Jo; Sang Hoon Kim; Ji-Eun Hwang; Ye-Sol Kim; Han Sol Kang; Se Won Kim; Soon-Jae Kwon; Jaihyunk Ryu; Jin-Baek Kim; Si-Yong Kang (Horticulture, Environment, and Biotechnology, 2016)

Spatial distribution of cold-adapted Synechococcus during spring in seas adjacent to Korea - Dong Han Choi; Jae Hoon Noh; Sung Min An; Yu Ri Choi; Howon Lee; Kongtae Ra; Dongseon Kim; TaeKeun Rho; Sang Heon Lee; Kyung-Tae Kim; Kyung-Il Chang; Jung Ho Lee (Algae, 2016)

Enhanced production of resveratrol derivatives in tobacco plants by improving the metabolic flux of intermediates in the phenylpropanoid pathway - Yu Jeong Jeong; Chul Han An; Su Gyeong Woo; Ji Hye Park; Ki-Won Lee; Sang-Hoon Lee; Yeonggil Rim; Hyung Jae Jeong; Young Bae Ryu; Cha Young Kim (Plant Molecular Biology, 2016)

Subacute Inhalation Toxicity of 3-Methylpentane - Yong Hyun Chung; Seo-Ho Shin; Jeong Hee Han; Yong-Hoon Lee (Toxicological Research, 2016)

Keeping house: evaluation of housekeeping genes for real-time PCR in the red alga, Bostrychia moritziana (Florideophyceae) - Junbo Shim; Eunyoung Shim; Gwang Hoon Kim; Jong Won Han; Giuseppe C. Zuccarello (Algae, 2016)

A field application feasibility assessment of naphthoquinone derivatives for the mitigation of freshwater diatom Stephanodiscus blooms - Jae-Hyoung Joo; Yoon-Ho Kang; Bum Soo Park; Chong-Sung Park; Hoon Cho; Myung-Soo Han (Journal of Applied Phycology, 2016)

Synthesis of silica encapsulated DVB nano-particles for toxicology application - Simranjeet Singh Sekhon; Jae-Min Park; Ji-Young Ahn; Kyeong-Ah Lee; Jung Ho Ko; Lyon Lee; Maisie Dawes; John Tyler; Janet Han; Sang Yong Kim; Jiho Min; Yang-Hoon Kim (Toxicology and Environmental Health Sciences, 2016)

Seismic reflection imaging of Quaternary faulting offshore the southeastern Korean Peninsula - Han-Joon Kim; YoungSook Baek; Hyeong-Tae Jou; Sang Hoon Lee; Seonghoon Moon; Jin Soo Kim; Su-hwan Lee; Gwang Hoon Lee; Seung-Goo Kang; Woo-Hyun Son; Ryeongsim Seok (Geosciences Journal, 2016)

Protective effect of a freshwater alga, Spirogyra sp., against lipid peroxidation in vivo zebrafish and purification of antioxidative compounds using preparative centrifugal partition chromatography - Ji-Hyeok Lee; Jong Won Han; Ju-Young Ko; Wonwoo Lee; Ginnae Ahn; Chul-Young Kim; Gwang Hoon Kim; You-Jin Jeon (Journal of Applied Phycology, 2016)

Matrix Metalloproteinase-8 is a Novel Pathogenetic Factor in Focal Cerebral Ischemia - Jeong Eun Han; Eun-Jung Lee; Eunjung Moon; Jong Hoon Ryu; Ji Woong Choi; Hee-Sun Kim (Molecular Neurobiology, 2016)

MeCP2 Modulates Sex Differences in the Postsynaptic Development of the Valproate Animal Model of Autism - Ki Chan Kim; Chang Soon Choi; Ji-Woon Kim; Seol-Heui Han; Jae Hoon Cheong; Jong Hoon Ryu; Chan Young Shin (Molecular Neurobiology, 2016)

Knockdown of HIF-1α and IL-8 induced apoptosis of hepatocellular carcinoma triggers apoptosis of vascular endothelial cells - Sung Hoon Choi; Jun Yong Park; Wonseok Kang; Seung Up Kim; Do Young Kim; Sang Hoon Ahn; Simon Wonsang Ro; Kwang-Hyub Han (Apoptosis, 2016)

Transcriptome analysis of the short-term photosynthetic sea slug Placida dendritica - Ji Hee Han; Tatyana A. Klochkova; Jong Won Han; Junbo Shim; Gwang Hoon Kim (Algae, 2015)

Statistical modeling for selecting a superior working dog using microsatellite loci - Hoim Jeong; Kyeongjun Lee; Bong-Hwan Choi; Hee-Eun Lee; Jeong-An Gim; Dong-Hoon Lee; Ji-Hong Ha; Kook-Il Han; Youngseuk Cho; Heui-Soo Kim (Genes & Genomics, 2015)

Niche partitioning of picocyanobacterial lineages in the oligotrophic northwestern Pacific Ocean - Dong Han Choi; Karen E. Selph; Jae Hoon Noh (Algae, 2015)

Effect of low temperature on Schwann-like cell differentiation of bone marrow mesenchymal stem cells - Hee-Hoon Yoon; Mi-Jung Han; Jung-Keug Park; Jong-Ho Lee; Young-Kwon Seo (Tissue Engineering and Regenerative Medicine, 2015)

Trace element analysis of three tissues from Eurasian otters (Lutra lutra) in South Korea - Sukmo Kang; Jung-Hoon Kang; Soohee Kim; Seung Heon Lee; Seungwoo Lee; Hee Jeong Yu; Su-Jun Oh; Jung-Duck Park; Ki-Hoan Nam; Sung Yong Han; Jong-Deock Lim; Doug-Young Ryu (Ecotoxicology, 2015)

Size-dependent clearance of gold nanoparticles from lungs of Sprague–Dawley rats after short-term inhalation exposure - Sung Gu Han; Jong Seong Lee; Kangho Ahn; Yong Soon Kim; Jin Kwon Kim; Ji Huyn Lee; Jae Hoon Shin; Ki Soo Jeon; Wan Seob Cho; Nam Woong Song; Mary Gulumian; Beom Soo Shin; et al. (Archives of Toxicology, 2015)

The influences of CYP2D6 genotypes and drug interactions on the pharmacokinetics of venlafaxine: exploring predictive biomarkers for treatment outcomes - Fen Jiang; Hae-Deun Kim; Han-Sung Na; Seok-Yong Lee; Doo-Won Seo; Jong-Yeol Choi; Ji-Hye Ha; Hee-Jung Shin; Young-Hoon Kim; Myeon-Woo Chung (Psychopharmacology, 2015)

Potential applications of nuisance microalgae blooms - Jang K. Kim; Sreejith Kottuparambil; Sang Hyun Moh; Taek Kyun Lee; Youn-Jung Kim; Jae-Sung Rhee; Eun-Mi Choi; Byung Hoon Kim; Yong Ju Yu; Charles Yarish; Taejun Han (Journal of Applied Phycology, 2015)

Glycan structure and serum half-life of recombinant CTLA4Ig, an immunosuppressive agent, expressed in suspension-cultured rice cells with coexpression of human β1,4-galactosyltransferase and human CTLA4Ig - Seung Hoon Kang; Hahn Sun Jung; Song Jae Lee; Cheon Ik Park; Sang Min Lim; Heajin Park; Byung Sun Kim; Kwang Heum Na; Gyeong Jin Han; Jae Woo Bae; Hyun Joo Park; Keuk Chan Bang; et al. (Glycoconjugate Journal, 2015)

Induction of GDNF and BDNF by hRheb(S16H) Transduction of SNpc Neurons: Neuroprotective Mechanisms of hRheb(S16H) in a Model of Parkinson’s Disease - Jin Han Nam; Eunju Leem; Min-Tae Jeon; Kyoung Hoon Jeong; Jeen-Woo Park; Un Ju Jung; Nikolai Kholodilov; Robert E. Burke; Byung Kwan Jin; Sang Ryong Kim (Molecular Neurobiology, 2015)

Identification of key factors influencing primary productivity in two river-type reservoirs by using principal component regression analysis - Yeonjung Lee; Sun-Yong Ha; Hae-Kyung Park; Myung-Soo Han; Kyung-Hoon Shin (Environmental Monitoring and Assessment, 2015)

Effects of the algicide, thiazolidinedione derivative TD49, on microbial communities in a mesocosm experiment - Moonho Son; Seung Ho Baek; Kyoungsoon Shin; Keun-Hyung Choi; Si Wouk Kim; Jaewon Ryu; Hoon Cho; Seung Won Jung; Ik Kyo Chung; Young-Ok Kim; Myung-Soo Han (Environmental Monitoring and Assessment, 2015)

Construction of target‐specific virus‐like particles for the delivery of algicidal compounds to harmful algae - Beom Sik Kang; Chi‐Yong Eom; Wonduck Kim; Pyoung il Kim; Sun Yi Ju; Jaewon Ryu; Gui Hwan Han; Jeong‐Il Oh; Hoon Cho; Seung Ho Baek; Gueeda Kim; Minju Kim; et al. (Environmental Microbiology, 2015)
Summary Harmful algal blooms ( HABs ) can lead to substantial socio‐economic losses and extensive damage to aquatic ecosystems, drinking water sources and human health. Common algicidal techniques, including ozonation, ultrasonic treatment and dispersion of algae‐killing chemicals, are unsatisfactory both economically and ecologically. This study therefore presents a novel alternative strategy for the efficient control of deleterious algae via the use of host‐specific virus‐like particles ( VLPs ) combined with chemically synthesized algicidal compounds. The capsid protein of HcRNAV34 , a single‐stranded RNA virus that infects the toxic dinoflagellate, H eterocapsa circularisquama , was expressed in and purified from E scherichia coli and then self‐assembled into VLPs in vitro . Next, the algicidal compound, thiazolidinedione 49 ( TD49 ), was encapsidated into HcRNAV34 VLPs for specific delivery to H . circularisquama . Consequently, HcRNAV34 VLPs demonstrated the same host selectivity as naturally occurring HcRNAV34 virions, while TD49 ‐encapsidated VLPs showed a more potent target‐specific algicidal effect than TD49 alone. These results indicate that target‐specific VLPs for the delivery of cytotoxic compounds to nuisance algae might provide a safe, environmentally friendly approach for the management of HABs in aquatic ecosystems.

Erratum to: Characterization of a GH family 8 β-1,3-1,4-glucanase with distinctive broad substrate specificity from Paenibacillus sp. X4 - Han Beur Na; Won Kyeong Jung; Yu Seok Jeong; Hee Jung Kim; Sung Kyum Kim; Jungho Kim; Han Dae Yun; Jung-Kul Lee; Hoon Kim (Biotechnology Letters, 2015)

Characterization of a GH family 8 β-1,3-1,4-glucanase with distinctive broad substrate specificity from Paenibacillus sp. X4 - Han Beur Na; Won Kyeong Jung; Yu Seok Jeong; Hee Jung Kim; Sung Kyum Kim; Jungho Kim; Han Dae Yun; Jung-Kul Lee; Hoon Kim (Biotechnology Letters, 2015)

Polymorphism analysis of tyrosine hydroxylase gene variable number of tandem repeats in various Korean dogs - Hee-Eun Lee; Bong-Hwan Choi; Dong-Hoon Lee; Yun-Jeong Kwon; Jungwoo Eo; Yuri Choi; Hoim Jeong; Jeong-An Gim; Tae-Hun Kim; Ji-Hong Ha; Kook-Il Han; Heui-Soo Kim (Genes & Genomics, 2015)

Identification of three proteins involved in fertilization and parthenogenetic development of a brown alga, Scytosiphon lomentaria - Jong Won Han; Tatyana A. Klochkova; Junbo Shim; Chikako Nagasato; Taizo Motomura; Gwang Hoon Kim (Planta, 2014)

Statistical analysis and genetic diversity of three dog breeds using simple sequence repeats - Hoim Jeong; Bong-Hwan Choi; Jungwoo Eo; Yun-Jeong Kwon; Hee-Eun Lee; Yuri Choi; Jeong-An Gim; Tae-Hun Kim; Hwan-Hoo Seong; Dong-Hoon Lee; Ji-Hong Ha; Kook-Il Han; et al. (Genes & Genomics, 2014)

Analysis of Cyazofamid and its Metabolite in the Environmental and Crop Samples Using LC–MS/MS - Hyeri Lee; Eunhye Kim; Jong-Hwa Lee; Jeong Hee Sung; Hoon Choi; Jeong-Han Kim (Bulletin of Environmental Contamination and Toxicology, 2014)

Multi-lineage differentiation of human mesenchymal stromal cells on the biophysical microenvironment of cell-derived matrix - Dong Hoon Choi; Muhammad Suhaeri; Mintai P. Hwang; Ik Hwan Kim; Dong Keun Han; Kwideok Park (Cell and Tissue Research, 2014)

Complete genome sequence of the Pectobacterium carotovorum subsp. carotovorum virulent bacteriophage PM1 - Jeong-A Lim; Hakdong Shin; Dong Hwan Lee; Sang-Wook Han; Ju-Hoon Lee; Sangryeol Ryu; Sunggi Heu (Archives of Virology, 2014)

Dioscin induces caspase-independent apoptosis through activation of apoptosis-inducing factor in breast cancer cells - Eun-Ae Kim; Ji-Hoon Jang; Yun-Han Lee; Eon-Gi Sung; In-Hwan Song; Joo-Young Kim; Suji Kim; Ho-Yong Sohn; Tae-Jin Lee (Apoptosis, 2014)

Prognosis of hepatocellular carcinoma patients with extrahepatic metastasis and the controllability of intrahepatic lesions - Jung Il Lee; Ja Kyung Kim; Do Young Kim; Sang Hoon Ahn; Jun Yong Park; Seung Up Kim; Beom Kyung Kim; Kwang Hyub Han; Kwan Sik Lee (Clinical & Experimental Metastasis, 2014)

tPA Regulates Neurite Outgrowth by Phosphorylation of LRP5/6 in Neural Progenitor Cells - Sung Hoon Lee; Hyun Myung Ko; Kyoung Ja Kwon; Jongmin Lee; Seol-Heui Han; Dong Wook Han; Jae Hoon Cheong; Jong Hoon Ryu; Chan Young Shin (Molecular Neurobiology, 2014)

Targeting Estrogen Receptors for the Treatment of Alzheimer’s Disease - Jung Hoon Lee; Yanxialei Jiang; Dong Hoon Han; Seung Kyun Shin; Won Hoon Choi; Min Jae Lee (Molecular Neurobiology, 2014)

The role of preameloblast-conditioned medium in dental pulp regeneration - Han-Wool Choung; Ji-Hyun Lee; Dong-Seol Lee; Pill-Hoon Choung; Joo-Cheol Park (Journal of Molecular Histology, 2013)

A proposal to unify two subspecies of Staphylococcus equorum: Staphylococcus equorum subsp. equorum and Staphylococcus equorum subsp. linens - Do-Won Jeong; Hye-Rim Kim; Seulhwa Han; Che Ok Jeon; Jong-Hoon Lee (Antonie van Leeuwenhoek, 2013)

Oseltamivir-resistant influenza viruses isolated in South Korea from 2005 to 2010 - Han-Gil Cho; Jang-Hoon Choi; Hyun-Kyung Lee; Su-Kyoung Mun; Jong-Bok Lee; Eek-Hoon Jho; Chun Kang; Young-Hee Lim (Archives of Virology, 2013)

An ELIP-like gene in the freshwater green alga, Spirogyra varians (Zygnematales), is regulated by cold stress and CO2 influx - Jong Won Han; Gwang Hoon Kim (Journal of Applied Phycology, 2013)

Expression of a lipase on the cell-surface of Escherichia coli using the OmpW anchoring motif and its application to enantioselective reactions - Hyuk Lee; Si Jae Park; Mee-Jung Han; Gyeong Tae Eom; Min-Jung Choi; Seong Ho Kim; Young Hoon Oh; Bong Keun Song; Seung Hwan Lee (Biotechnology Letters, 2013)

Class 3 inhibition of hERG K+ channel by caffeic acid phenethyl ester (CAPE) and curcumin - Seong Woo Choi; Kyung Su Kim; Dong Hoon Shin; Hae Young Yoo; Han Choe; Tae Hee Ko; Jae Boum Youm; Woo Kyung Kim; Yin Hua Zhang; Sung Joon Kim (Pflügers Archiv - European Journal of Physiology, 2013)

Erratum to: Accumulation of galloyl derivatives in a green alga, Spirogyra varians, in response to cold stress - Jong Won Han; Minchul Yoon; Frithjof C. Küpper; Tatyana A. Klochkova; Jung-Soon Oh; Jung-Rae Rho; Gwang Hoon Kim (Journal of Applied Phycology, 2013)

Docetaxel-Loaded Thermosensitive and Bioadhesive Nanomicelles as a Rectal Drug Delivery System for Enhanced Chemotherapeutic Effect - Youn Gee Seo; Dong-Wuk Kim; Woo Hyun Yeo; Thiruganesh Ramasamy; Yu-Kyoung Oh; Young-Joon Park; Jung-Ae Kim; Dong Hoon Oh; Sae Kwang Ku; Jin Ki Kim; Chul Soon Yong; Jong Oh Kim; et al. (Pharmaceutical Research, 2013)

Delphinidin prevents hypoxia-induced mouse embryonic stem cell apoptosis through reduction of intracellular reactive oxygen species-mediated activation of JNK and NF-κB, and Akt inhibition - Bit Na Seo; Jung Min Ryu; Seung Pil Yun; Ji Hoon Jeon; Su Shin Park; Keon Bong Oh; Jin-Ki Park; Ho Jae Han (Apoptosis, 2013)

Ionizing radiation-inducible microRNA miR-193a-3p induces apoptosis by directly targeting Mcl-1 - Jeong-Eun Kwon; Bu-Yeon Kim; Seo-Young Kwak; In-Hwa Bae; Young-Hoon Han (Apoptosis, 2013)

Cold-tolerant strain of Haematococcus pluvialis (Haematococcaceae, Chlorophyta) from Blomstrandhalvøya (Svalbard) - Tatyana A. Klochkova; Min Seok Kwak; Jong Won Han; Taizo Motomura; Chikako Nagasato; Gwang Hoon Kim (Algae, 2013)

Morphology, molecular phylogeny and photosynthetic activity of the sacoglossan mollusc, Elysia nigrocapitata, from Korea - Tatyana A. Klochkova; Jong Won Han; Kyong-Hwa Chah; Ro Won Kim; Ju-Hyoung Kim; Kwang Young Kim; Gwang Hoon Kim (Marine Biology, 2013)

High prevalence of amantadine-resistant influenza A virus isolated in Gyeonggi Province, South Korea, during 2005–2010 - Han-Gil Cho; Jang-Hoon Choi; Woon-Ho Kim; Hae-Kun Hong; Mi-Hye Yoon; Eek-Hoon Jho; Chun Kang; Young-Hee Lim (Archives of Virology, 2013)

Generation and evaluation of the efficacy of rhesus monkey soluble cytotoxic T lymphocyte-associated antigen-4 in the allogeneic mixed lymphocyte reaction - Jung-Sik Kim; Inho Choi; Han-Hyoung Lee; Suk Jun Lee; Manheum Na; Sang-Hoon Kim; Jihye Han; Joonbeom Bae; Sang-Pil Choi; Sang Joon Kim; Chung-Gyu Park; Taehoon Chun (Biotechnology Letters, 2012)

The effect of sRAGE-Fc fusion protein attenuates inflammation and decreases mortality in a murine cecal ligation and puncture model - Su Jin Jeong; Beom Jin Lim; Sungha Park; Donghoon Choi; Hye Won Kim; Nam Su Ku; Sang Hoon Han; Chang Oh Kim; Jun Yong Choi; Young Goo Song; June Myung Kim (Inflammation Research, 2012)

Accumulation of galloyl derivatives in a green alga, Spirogyra varians, in response to cold stress - Jong Won Han; Minchul Yoon; Frithjof D. Kupper; Tatyana A. Klochkova; Jung-Soon Oh; Jung-Rae Rho; Gwang Hoon Kim (Journal of Applied Phycology, 2012)

Estimation of the minimum food requirement using the respiration rate of medusa of Aurelia aurita in Sihwa Lake - Chang-hoon Han; Jinho Chae; Jonghyeok Jin; Wonduk Yoon (Ocean Science Journal, 2012)

Biomass and trophic structure of the plankton community in subtropical and temperate waters of the northwestern Pacific Ocean - Chang-Rae Lee; Keun-Hyung Choi; Hyung-Ku Kang; Eun Jin Yang; Jae Hoon Noh; Dong Han Choi (Journal of Oceanography, 2012)

Prevalence and genetic characterization of respiratory syncytial virus (RSV) in hospitalized children in Korea - Yun Hee Baek; Eun Hye Choi; Min-Suk Song; Philippe Noriel Q. Pascua; Hyeok-il Kwon; Su-Jin Park; Jun Han Lee; Sung-Il Woo; Byung-Hoon Ahn; Heon-Seok Han; Yoon-Soo Hahn; Kyeong-Seob Shin; et al. (Archives of Virology, 2012)

Activation of a flavin monooxygenase gene YUCCA7 enhances drought resistance in Arabidopsis - Minyoung Lee; Jae-Hoon Jung; Doo-Yeol Han; Pil Joon Seo; Woong June Park; Chung-Mo Park (Planta, 2012)

Molecular characterization of a lectin, BPL-4, from the marine green alga Bryopsis plumosa (Chlorophyta) - Jong-Won Han; Kang-Sup Yoon; Min-Gui Jung; Kyong-Hwa Chah; Gwang-Hoon Kim (Algae, 2012)

Influence of salinity on metal toxicity to Ulva pertusa - Jeong-ju Oh; Eun-Mi Choi; Young-Seok Han; Jeong-Hyun Yoon; Areum Park; Kyosun Jin; Ju-Wook Lee; Hoon Choi; Sunjin Kim; Murray T. Brown; Taejun Han (Toxicology and Environmental Health Sciences, 2012)

Isolation of cold-responsive genes from garlic, Allium sativum - Jae-Han Son; Kyong-Cheul Park; Sung-Il Lee; Haeng-Hoon Kim; Jong-Hwa Kim; Sun-Hyung Kim; Nam-Soo Kim (Genes & Genomics, 2012)

A synergetic approach to estimating timber age using integrated remotely sensed optical image and InSAR height data - Changjae Kim; Joon Heo; Jung Bin Lee; Soohee Han; Jae Hoon Jung; Shanmuganathan Jayakumar (International Journal of Remote Sensing, 2012)

Picocyanobacterial abundances and diversity in surface water of the northwestern Pacific Ocean - Dong Han Choi; Jae Hoon Noh; Mi-Seon Hahm; Charity Mijin Lee (Ocean Science Journal, 2011)

Sensitivity of spore germination and germ tube elongation of Saccharina japonica to metal exposure - Taejun Han; Jeong-Ae Kong; Hee-Gyu Kang; Seon-Jin Kim; Gyo-Sun Jin; Hoon Choi; Murray T. Brown (Ecotoxicology, 2011)

Expression of myeloperoxidase in swine influenza virus (SIV)-infected neutrophils in lungs from pigs experimentally infected with SIV subtype H1N2 - Bongtae Kim; Jeoung Hwa Shin; Kiwon Han; Hwi Won Seo; Yeonsu Oh; Ikjae Kang; Changhoon Park; Bog-Hieu Lee; Jin Sil Jang; Sung-Hoon Kim; Chanhee Chae (Veterinary Research Communications, 2011)

Purification and characterization of a lectin, BPL-3, from the marine green alga Bryopsis plumosa - Jong Won Han; Kang Sup Yoon; Tatyana A. Klochkova; Mi-Sook Hwang; Gwang Hoon Kim (Journal of Applied Phycology, 2011)

Effect of fiducial marker defects on stereotactic target localization in the Leksell stereotactic system - Jeong-Hoon Park; Jung Ho Han; Chae-Yong Kim; Chang Wan Oh; Dong Gyu Kim; Tae-Suk Suh; Hyun-Tai Chung (Medical & Biological Engineering & Computing, 2011)

The Protective Effect of ENA Actimineral Resource A on CCl4-Induced Liver Injury in Rats - Il-Hwa Hong; Hoon Ji; Sung-Yong Hwa; Won-Il Jeong; Da-Hee Jeong; Sun-Hee Do; Ji-Min Kim; Mi-Ran Ki; Jin-Kyu Park; Moon-Jung Goo; Ok-Kyung Hwang; Kyung-Sook Hong; et al. (Marine Biotechnology, 2011)

Expression of mucins on the mucosal surface of lungs of 4-week-old pigs - Chung Hyun Kim; Kichan Lee; Kiwon Han; Yeonsu Oh; Duyeol Kim; Hwi Won Seo; Changhoon Park; Mi-Kyoung Ha; Sung-Hoon Kim; Kyung-Dong Cho; Bog-Hieu Lee; Chanhee Chae (Veterinary Research Communications, 2011)

Comparative proteomics of the mixotrophic dinoflagellate Prorocentrum micans growing in different trophic modes - Jun-Bo Shim; Tatyana A. Klochkova; Jong-Won Han; Gwang-Hoon Kim; Yeong-Du Yoo; Hae-Jin Jeong (Algae, 2011)

Blue LED and succinic acid enhance the growth of Rhodobacter sphaeroides - Hyun Jeong Lee; Ju-Yong Park; Chul-Hee Han; Suk-Tai Chang; Yang-Hoon Kim; Jiho Min (World Journal of Microbiology and Biotechnology, 2011)

Comparative global transcription analysis of Aconitum koreanum Raymond, Typhonium gigantum Engl., and Helianthus tuberosis Linne - Ki Suk Kim; Jin Tae; Jung Bum Han; Kwang Seok Ahn; Beom-Joon Lee; Seok-Geun Lee; Jun-Hee Lee; Sung-Hoon Kim; Ho young Choi; Hyeung-Jin Jang (Molecular & Cellular Toxicology, 2010)

Characterization of carbohydrate combining sites of Bryohealin, an algal lectin from Bryopsis plumosa - Min Gui Jung; Key Pyoung Lee; Han-Gu Choi; Sung-Ho Kang; Tatyana A. Klochkova; Jong Won Han; Gwang Hoon Kim (Journal of Applied Phycology, 2010)

Feeding specificity and photosynthetic activity of Korean sacoglossan mollusks - Tatyana A. Klochkova; Jong-Won Han; Ju-Hyoung Kim; Kwang-Young Kim; Gwang-Hoon Kim (Algae, 2010)

Cytoskeletal changes during nuclear and cell division in the freshwater alga Zygnema cruciatum (Chlorophyta, Zygnematales) - Min-Chul Yoon; Jong-Won Han; Mi-Sook Hwang; Gwang-Hoon Kim (Algae, 2010)

Advances in biodiesel fuel for application in compression ignition engines - Jo-Han Ng; Hoon Kiat Ng; Suyin Gan (Clean Technologies and Environmental Policy, 2010)

Role of (−)-epigallocatechin-3-gallate in cell viability, lipogenesis, and retinol-binding protein 4 expression in adipocytes - Hye-Young Sung; Chae-Geun Hong; Young-Sung Suh; Ho-Chan Cho; Jae-Hyung Park; Jae-Hoon Bae; Won-Kyun Park; Jin Han; Dae-Kyu Song (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Gentamicin-Loaded Wound Dressing With Polyvinyl Alcohol/Dextran Hydrogel: Gel Characterization and In Vivo Healing Evaluation - Ma-Ro Hwang; Jong Oh Kim; Jeong Hoon Lee; Yong Il Kim; Jeong Hoon Kim; Sun Woo Chang; Sung Gju Jin; Jung Ae Kim; Won Seok Lyoo; Sung Soo Han; Sae Kwang Ku; Chul Soon Yong; et al. (AAPS PharmSciTech, 2010)

Isolation of a novel gene encoding a 3,5,6-trichloro-2-pyridinol degrading enzyme from a cow rumen metagenomic library - Renukaradhya K. Math; Shah Md. Asraful Islam; Kye Man Cho; Sun Joo Hong; Jong Min Kim; Myoung Geun Yun; Ji Joong Cho; Jae Young Heo; Young Han Lee; Hoon Kim; Han Dae Yun (Biodegradation, 2010)

Brown algae (Phaeophyceae) from Russian Far Eastern seas: re-evaluation of Laminaria multiplicata Petrov et Suchovejeva - Tatyana A. Klochkova; Gwang-Hoon Kim; Kyung-Min Lee; Han-Gu Choi; Mihail N. Belij; Nina G. Klochkova (Algae, 2010)

Three AFLP markers tightly linked to the genic male sterility ms 3 gene in chili pepper (Capsicum annuum L.) and conversion to a CAPS marker - Jundae Lee; Jae Bok Yoon; Jung-Heon Han; Won Phil Lee; Sang Hoon Kim; Hyo Guen Park (Euphytica, 2010)

Rapid detection of virulence stx2 gene of Enterohemorrhagic Escherichia coli using two-step ultra-rapid real-time PCR - Il-Wook Kim; Min-Hee Kang; Soon-Hwan Kwon; Seung-Hak Cho; Byung-Sun Yoo; Sang-Hoon Han; Byoung-Su Yoon (Biotechnology Letters, 2010)

A comparative analysis of the complete mitochondrial genome of the Eurasian otter Lutra lutra (Carnivora; Mustelidae) - Jang-Seu Ki; Dae-Sik Hwang; Tae-Jin Park; Sang-Hoon Han; Jae-Seong Lee (Molecular Biology Reports, 2010)

Changes in the frequency, scale, and failing areas of latest Quaternary (<29.4 cal. ka B.P.) slope failures along the SW Ulleung Basin, East Sea (Japan Sea), inferred from depositional characters of densely dated turbidite successions - Sang Hoon Lee; Jang J. Bahk; Han J. Kim; Kyung E. Lee; Hyeong T. Jou; Bong C. Suk (Geo-Marine Letters, 2010)

Seismic character of the BSR in the Ulleung Basin plain, East Sea (Japan Sea) - Han-Joon Kim; Gwang Hoon Lee; Hyeong-Tae Jou; Sang Hoon Lee; Dong-Geun Yoo; Nam-Hyung Koo; Gap-Sik Jeong; Bong-Chool Suk (Geosciences Journal, 2010)

Soluble pig lymphocyte activation gene-3 (LAG-3; CD223) inhibits human-to-pig xenogeneic mixed lymphocyte reaction - Seon-Soo Kim; Hyun-Jung Byun; Sang-Hoon Kim; Han-Hyoung Lee; Suk Jun Lee; Sang Joon Kim; Chung-Gyu Park; Taehoon Chun (Biotechnology Letters, 2010)

Control of Algal Scum Using Top-Down Biomanipulation Approaches and Ecosystem Health Assessments for Efficient Reservoir Management - Kwang-Guk An; Jae-Yon Lee; Hema K. Kumar; Sang-Jae Lee; Soon-Jin Hwang; Baik-Ho Kim; Young-Seuk Park; Kyung-Hoon Shin; Sangkyu Park; Han-Yong Um (Water, Air, & Soil Pollution, 2010)

Virulotyping of Salmonella enterica subsp. enterica isolated from indigenous vegetables and poultry meat in Malaysia using multiplex-PCR - Chai-Hoon Khoo; Yoke-Kqueen Cheah; Learn-Han Lee; Jiun-Horng Sim; Noorzaleha Awang Salleh; Shiran Mohd Sidik; Son Radu; Sabrina Sukardi (Antonie van Leeuwenhoek, 2009)

Molecular characterization and physico-chemical analysis of a new giant embryo mutant allele (ge t) in rice (Oryza sativa L.) - Dong-Soo Park; Soo-Kwon Park; Bong-Chun Lee; Song-Yi Song; Nam-Soo Jun; Norvie L. Manigbas; Jun-Hyun Cho; Min-Hee Nam; Jong-Seong Jeon; Chang-Deok Han; Kyung-Jin Choi; Doh-Hoon Kim; et al. (Genes & Genomics, 2009)

Reduction of ischemia-induced cerebral injury by all-trans-retinoic acid - Byung-Kwan Choi; Ji-Hoon Kim; Jong-Soo Jung; Young-Suk Lee; Myoung-Eun Han; Sun-Yong Baek; Bong-Seon Kim; Jae-Bong Kim; Sae-Ock Oh (Experimental Brain Research, 2009)

Physiological differences in the growth of Sargassum horneri between the germling and adult stages - Han Gil Choi; Ki Hoon Lee; Hyun Il Yoo; Pil Jun Kang; Young Sik Kim; Ki Wan Nam (Journal of Applied Phycology, 2008)

Analysis of Salmonella Agona and Salmonella Weltevreden in Malaysia by PCR fingerprinting and antibiotic resistance profiling - Lee Learn-Han; Cheah Yoke-Kqueen; Noorzaleha Awang Salleh; Sabrina Sukardi; Sim Jiun-Horng; Khoo Chai-Hoon; Son Radu (Antonie van Leeuwenhoek, 2008)

SLC11A1 Polymorphisms Are Associated with the Risk of Chronic Obstructive Pulmonary Disease in a Korean Population - Eun Jin Kim; Kyung Mee Kim; Sun Ha Park; Jong Sik Kim; Won Kee Lee; Sung Ick Cha; Chang Ho Kim; Young Mo Kang; Sung Beom Han; Tae Hoon Jung; Jae Yong Park (Biochemical Genetics, 2008)

Comparative Analysis of the glg Operons of Pectobacterium chrysanthemi PY35 and Other Prokaryotes - Kye Man Cho; Woo Jin Lim; Renukaradhya K. Math; Shah Md. Asraful Islam; Sun Joo Hong; Hoon Kim; Han Dae Yun (Journal of Molecular Evolution, 2008)

Changes in the activity of the multifunctional β-glycosyl hydrolase (Cel44C-Man26A) from Paenibacillus polymyxa by removal of the C-terminal region to minimum size - Kye-Man Cho; Renukaradhya K. Math; Su-Young Hong; Shah Md. Asraful Islam; Jong-Ok Kim; Sun-Joo Hong; Hoon Kim; Han-Dae Yun (Biotechnology Letters, 2008)

15-Deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) sensitizes human leukemic HL-60 cells to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis through Akt downregulation - Hoon Han; Sung-Won Shin; Chi-Yeon Seo; Hyuk-Chan Kwon; Jin-Yeong Han; In-Hoo Kim; Jong-Young Kwak; Joo-In Park (Apoptosis, 2007)

Construction of the bifunctional enzyme cellulase-β-glucosidase from the hyperthermophilic bacterium Thermotoga maritima - Su-Young Hong; Jin-Suk Lee; Kye-Man Cho; Renukaradhya K. Math; Yong-Hee Kim; Sun-Joo Hong; Yong-Un Cho; Soo-Jeong Cho; Hoon Kim; Han-Dae Yun (Biotechnology Letters, 2007)

Identification and Isolation of Differentially Expressed Gene in Response to Cold Stress in a Green Alga, Spirogyra varians (Zygnematales) - Jong-Won Han; Min-Chul Yoon; Key-Pyoung Lee; Gwang-Hoon Kim (Algae, 2007)

Isolation of Total RNA from a Freshwater Green Alga, Zygnema cruciatum, Containing High Levels of Pigments - Jong-Won Han; Min-Chul Yoon; Key-Pyoung Lee; Gwang-Hoon Kim (Algae, 2007)

OECD validation of the rodent Hershberger assay using three reference chemicals; 17α-methyltestosterone, procymidone, and p,p′-DDE - Jae-Ho Shin; Hyun Ju Moon; Il Hyun Kang; Tae Sung Kim; Su Jung Lee; Ji Youn Ahn; Hoon Bae; Eui Bae Jeung; Soon Young Han (Archives of Toxicology, 2007)

A phosphate starvation-induced acid phosphatase from Oryza sativa: phosphate regulation and transgenic expression - Yeon Jae Hur; Han Gil Lee; Eun Ji Jeon; Yun Young Lee; Min Hee Nam; Gihwan Yi; Moo Young Eun; Jaesung Nam; Jai Heon Lee; Doh Hoon Kim (Biotechnology Letters, 2007)

Geochemical characterization of the organic matter, pore water constituents and shallow methane gas in the eastern part of the Ulleung Basin, East Sea (Japan Sea) - Ji‐Hoon Kim; Myong‐Ho Park; Urumu Tsunogai; Tae‐Jin Cheong; Byong‐Jae Ryu; Young‐Joo Lee; Hyun‐Chul Han; Jae‐Ho Oh; Ho‐Wan Chang (Island Arc, 2007)
Geochemical analyses of sediments, pore water and headspace gas of the piston cores taken from the eastern part of Ulleung Basin of the East Sea (Japan Sea) were carried out to assess the origin of the sedimentary organic matter and interstitial fluid. Several tephra layers within the core are identified as the Ulleung‐Oki (10.1 ka), the Aira‐Tanzawa (23 ka) and the Ulleung‐Yamato (30.9 ka) tephras. With the exception of these volcanic layers, the cores consist predominantly of muddy sediments that contain >0.5% total organic carbon. Atomic C/N ratios and δ 13 C org values suggest that the organic matter originated from marine algae rather than from land vascular plants, whereas Rock‐Eval pyrolysis suggests that the organic matter is thermally immature and comes from a land vascular plant (Type III). These conflicting results seem to be caused by the heavy oxidization of the marine organic matter. Sulphate concentration profiles of pore waters show strongly linear depletion ( r 2 > 0.97) with sediment depth. The estimated sulphate–methane interface (SMI) depth using the sulphate concentration gradient was nearly 3.5 m below seafloor (mbsf) in the southern part of the study area, and deeper than 6 mbsf in the northern part of the area. The difference in SMI depths is likely associated with the amount of the methane flux. The methane concentration below the SMI in the two southern cores increases rapidly, implying the occurrence of methanogenesis and anaerobic methane oxidation (AMO). In contrast, the two northern cores have a low methane concentration below the SMI. values measured from all cores were in the range of −83.5 to −69.5‰, which suggests that the methane derives from a methanogenic microbe. values become decreased toward SMI, but increased below SMI; therefore, has eventually the minimum value near the SMI. The values are also decreased when the methane concentration is increased. These phenomena support the typical occurrence of AMO in the study area.

Assembling a novel bifunctional cellulase–xylanase from Thermotoga maritima by end-to-end fusion - Su Young Hong; Jin Suk Lee; Kye Man Cho; Renukaradhya K Math; Yong Hee Kim; Sun Joo Hong; Yong Un Cho; Hoon Kim; Han Dae Yun (Biotechnology Letters, 2006)

Anti-apoptotic Activity of Laminarin Polysaccharides and their Enzymatically Hydrolyzed Oligosaccharides from Laminaria japonica - Ki-Hoon Kim; Yea-Woon Kim; Han Bok Kim; Burm Jong Lee; Dong Seok Lee (Biotechnology Letters, 2006)

Tsc-22 enhances TGF-? signaling by associating with Smad4 and induces erythroid cell differentiation - So-Jung Choi; Jae-Hoon Moon; Young-Wook Ahn; Jin-Hyun Ahn; Dong-Uk Kim; Tae-Hee Han (Molecular and Cellular Biochemistry, 2005)

Overexpression of human erythropoietin (EPO) affects plant morphologies: retarded vegetative growth in tobacco and male sterility in tobacco and Arabidopsis - Ban Yoon Cheon; Hae Jin Kim; Kyung Hee Oh; Sung Chul Bahn; Ji Hoon Ahn; Jang Won Choi; Sung Han Ok; Jung Myung Bae; Jeong Sheop Shin (Transgenic Research, 2004)

Timing of trap formation in the southwestern margin of the Ulleung Basin, East Sea (Japan Sea) and implications for hydrocarbon accumulations - Gwang Hoon Lee; Booyong Kim; Sung Jin Chang; Sik Huh; Han-Joon Kim (Geosciences Journal, 2004)

Comparative study of cholinergic cells in retinas of various mouse strains - Tae-Hoon Kang; Young-Han Ryu; In-Beom Kim; GooTaeg Oh; Myung-Hoon Chun (Cell and Tissue Research, 2004)

Netplankton Chlorophyll Biomass along 175°E in the Pacific Ocean - Dong-Hoon Han; Tohru Ikeya; Masayuki Mac Takahashi (Journal of Oceanography, 2004)

Optimization of Bifidobacterium longum growth by use of calcium carbonate-alginate beads - Su-Han Song; Teak-Bum Kim; Hoon-Il Oh; Deok-Kun Oh (World Journal of Microbiology and Biotechnology, 2003)

Intracellular drug delivery using poly(d,l-lactide-co-glycolide) nano- particles derivatized with a peptide from a transcriptional activator protein of HIV-1 - Yoon Sung Nam; Ju Young Park; Sang-Hoon Han; Ih-Seop Chang (Biotechnology Letters, 2002)

Changes of Flow Characteristics by Stenting in Aneurysm Models: Influence of Aneurysm Geometry and Stent Porosity - Kyehan Rhee; Moon Hee Han; Sang Hoon Cha (Annals of Biomedical Engineering, 2002)

A Spatial Aspect on Mitochondrial DNA Genealogy in Apodemus peninsulae from East Asia - Keiko Serizawa; Hitoshi Suzuki; Masahiro A. Iwasa; Kimiyuki Tsuchiya; Marina V. Pavlenko; Irina V. Kartavtseva; Galina N. Chelomina; Nikolai E. Dokuchaev; Sang-Hoon Han (Biochemical Genetics, 2002)

Expression and purification of Listeria innocua Sv6b p60 invasion associated protein - Yong-Hee Choi; Sang-Hoon Han; Yong-Soon Lee; Yoon-Kyu Lim; In-Gyu Kim; Byoung-Su Yoon (Biotechnology Letters, 2001)

Chlorophyll a Biomass of Netplankton in Surface Waters in the Pacific Sector of the Southern Ocean in Austral Summer - Dong-Hoon Han; Masayuki Mac Takahashi (Journal of Oceanography, 2001)

Promotion of conidial head formation in Aspergillus oryzae by a salt - Myung Hoon Song; Ju-young Nah; Yeon Soo Han; Dong Min Han; Keon-Sang Chae (Biotechnology Letters, 2001)

Chlorophyll a Biomass of Netplankton in Surface Waters of the Northern North Pacific Ocean and the Adjacent Seas from Summer to Autumn - Dong-Hoon Han; Masayuki Mac Takahashi (Journal of Oceanography, 2000)

Activities of sulfhydryl-related and phenylpropanoid-synthesizing enzymes during the germination ofArabidopsis thaliana seeds - Keum -Nam Park; Jae -Hoon Sa; Byung -Don Han; Eun -Hee Park; Chang -Jin Lim (Journal of Plant Biology, 1998)

Seismic study of the Ulleung Basin crust and its implications for the opening of the East Sea (Japan Sea) - Han-Joon Kim; Sang-Joon Han; Gwang Hoon Lee; Sik Huh (Marine Geophysical Research, 1998)